Correction to: Rosuvastatin-Loaded Glycerosomes as a Neuroprotective Strategy Against Hyperlipidemia-Induced Brain Dysfunction: Development, Optimization, and in vivo Evaluation - Mahran Mohamed Abd El-Emam; Mohamed Ibrahim; Milad Reda Qelliny; Mahmoud Mostafa; Marwa Mohamed El Sayed; Maha S. Kilany; Amira Ebrahim Alsemeh; Rania Said Moawad; Mohamed Fouad Mansour (Journal of Pharmaceutical Innovation, 2027)

Correction: Naringenin attenuates amiodarone-induced pulmonary fibrosis in rats via modulation of the SIRT1/NF-κB signalling pathway - Heba M. Arakeep; Wafaa Abdelaziz Emam; Amena Rezk Mohammed; Marwa H. Sedira; Marwa Mahmoud Awad; Alshimaa Aboalsoud; Rehab Ahmed Ahmed El-Shaer; Azza Mostafa Mohammed Aboshanady; Norhan Ahmed AbuoHashish (Molecular Biology Reports, 2026)

Naringenin attenuates amiodarone-induced pulmonary fibrosis in rats via modulation of the SIRT1/NF-κB signalling pathway - Heba M. Arakeep; Wafaa Abdelaziz Emam; Amena Rezk Mohammed; Marwa H Sedira; Marwa Mahmoud Awad; Alshimaa Aboalsoud; Rehab Ahmed Ahmed El-Shaer; Azza Mostafa Mohammed Aboshanady; Norhan Ahmed AbuoHashish (Molecular Biology Reports, 2026)

Post-thaw quality, apoptosis, oxidative stress, microbiota, and in vivo fertility of buffalo bull semen in response to quercetin nano-emulsion or hesperidin-loaded chitosan nanoparticles supplementation - Wael A. Khalil; Aya A. Ismail; Mahmoud A.E. Hassan; Mohamed M. Hegazy; Mostafa A. El-Harairy; Sameh A. Abdelnour; Mahmoud Moussa (Animal Reproduction Science, 2026)

An innovative, and sustainable approach to enhance physiological, biochemical, and molecular traits in tomato (Solanum lycopersicum Mill.) plant using naturally synthesized nanoparticles - Nermen Mahmoud; Ibrahim A. Hassan; Mohamed E. Hagar; Aly Mostafa (Physiological and Molecular Plant Pathology, 2026)

Innovative nanotechnology approach using salicylic acid loaded chitosan nanoparticles to improve post-thaw sperm function, reduce apoptosis, and preserve ultrastructure in rams - Wael A. Khalil; Azza S. El-Demerdash; Mahmoud A. E. Hassan; Khaled Fathy; Sherif M. Dessouki; Mostafa A. El-Harairy; Aya A. Ismail; Ali A. El-Raghi (Tropical Animal Health and Production, 2026)

Rosemary (Rosmarinus officinalis) Extract Attenuates Methotrexate-Induced Oxidative Stress, Inflammatory Disturbance, and Apoptotic Lung Injury: A Molecular and Histopathological Study - Abd El Ghany A. Moustafa; Aly Fahmy Mohamed; Ibrahim M. Ibrahim Amr; Hassan Fathy Kaabo; Laila El-sayed El-moselhy; Tamer Albasyoni Gomah; Amer M. Abdel Hamid; Amal Mahmoud Hammad; Walid Mostafa Sayed Ahmed; Fawzy Mahmoud Abou Galala; Fayez Mohammed Abd Elfattah Elbayoumy; Mohamed E. Amer; et al. (Cell Biochemistry and Biophysics, 2026)

Comprehensive evaluation of Balanites aegyptiaca extracts: in vitro bioactivities and in vivo antimicrobial efficacy and hematological impact on broiler chickens challenged with E. coli O78 and Clostridium perfringens type A - Asmaa Ezzat; Heba M. Salem; Sara H. Mahmoud; Ahmed Mostafa; Mohamed A. Ali; Khaled Mahmoud; Nasser S. Flefil; Tarek N. Soliman; Asmaa Negm El-Dein (Veterinary Research Communications, 2026)

Type 2 Diabetes-Induced Molecular and Functional Impairment of Adipose Tissue-Derived Mesenchymal Stromal Cells (ASCs) and Interferon Gamma Priming for Enhanced Diabetic ASC-Based Therapy - Alaa Zeinhom; Ammar Y. Mohamed; Nahla N. Abdel-Aziz; Mostafa Sayed Diab; Amir M. H. Salem; Noha N. Yassen; Eman E. A. Mohammed; Amal M. Mohamed; Ola M. Eid; Shymaa H. Hussein; Marwa Farid; Engy K. Tharwat; et al. (Stem Cell Reviews and Reports, 2026)

Sustainable Treatment of Highly Stabilized Oil-in-Water Emulsions Using Newly Synthesized PVC Nanocomposite Membranes Integrated with Magnetically Responsive Natural Waste-Derived Nanosilica Core-Shell - Hany M. Youssef; Rana H. M. El Hady Gheith; Mostafa M. H. Khalil; Mahmoud F. Mubarak; Sameh A. Elbanna; Hanan A. Ahmed (International Journal of Environmental Research, 2026)

Medication adherence in breast cancer: a comparative analysis of self-report tools and prescription refill data - Abdel-Hameed I. Ebid; Rana Elshewy; Mahmoud I. Mostafa; Reem Eid; Mohamed A. Mobarez; Emad Shash (European Journal of Clinical Pharmacology, 2026)

SIRT1 in brain aging: molecular mechanisms and therapeutic potential of pharmacological and natural modulators - Esraa M. Mosalam; Mahmoud S. Abdallah; Ahmed R. Gardouh; Eman Hamza; Mostafa M. Bahaa; Mahmoud Nazih; Reham A. Al-Dhelaan; Noha Kamal (Biogerontology, 2026)

Bioequivalence study of Prontogest 100 mg/2 mL solution for intramuscular injection versus reference progesterone injection, USP 500 mg/10 mL under fasting conditions: a randomized, open-label, two-sequence, four-period, fully replicated crossover study in healthy postmenopausal women - Yasser H. Habib; Mostafa Salah; Eman Galal; Amira Gouda; Youmna Mosaad; Mourad Ali; Amina Mahmoud; Noran Habib; Mosaad Morsi (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Retinoic acid disrupts cumulus granulosa cells function via EGFR downregulation: induction of PCOS and infertility in adult female mice - Ahmed Said; Mostafa Marzouk; Abdelrahman Mahmoud; Mohamed Emad; Mostafa Elkhbery; Khairiah Mubarak Alwutayd; Mariam Abdulaziz Alkhateeb; Murdhy A. Aldawsari; Abd Elaziz Shokry; Amira S. AbdElkhalek (Histochemistry and Cell Biology, 2026)

Correction: Scrutinizing the Feasibility of Nonionic Surfactants to Form Isotropic Bicelles of Curcumin: a Potential Antiviral Candidate Against COVID-19 - Dina B. Mahmoud; Mohamed Mofreh Bakr; Ahmed A. Al-karmalawy; Yassmin Moatasim; Ahmed El Taweel; Ahmed Mostafa (AAPS PharmSciTech, 2026)

EGCG-mediated selenium nanoparticles protect against 5-fluorouracil–induced cardiotoxicity via Nrf2/Keap1 signaling - Khaled M. Alam-ElDein; Moustafa Mahmoud Abdelaziz; Salma Sabry Elgezery; Youssef Tarek Fouad; Miriam Amir Mousa; Ahmed M. Elmosilhi; Malak Mostafa Mohamed; Salma A. Abdo; Mennatallah T. Ali; Basmala Shaher Mohamed; Radwa A. Hanafy; Alzahraa A. Elhemiely; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Phytochemical characterization and in vivo assessment of the anti-inflammatory and hepatoprotective properties of Cynanchum radians against acetaminophen-induced hepatotoxicity - Rwaida A. Al Haidari; Bandar D. Alrehaili; Sultan A. Almohammadi; Omar Hussain Alahmadi; Faisal Abdulrahman Alamri; Abdullah Osama Tarrazi; Mahmoud A. H. Mostafa (Natural Product Research, 2026)

Innovative Non-destructive Sugarcane Height Estimation via Satellite Imagery and Machine Learning - Mostafa Khosravirad; Mahmoud Omid; Fereydoun Sarmadian; Soleiman Hosseinpour (Agricultural Research, 2026)

Nano-liposomal berberine and vildagliptin combination: A novel therapeutic approach against oxidative stress, inflammation, autophagy dysregulation, and fibrosis in diabetic nephropathy - Areej A. Eskandrani; Safaa I. Khater; Mahran Mohamed Abd El-Emam; Rawan Altalhi; Mohamed M.M. Metwally; Tarek Khamis; Mahmoud Mostafa; Mohamed Mohamed Soliman; Shatha B. Albattal; Saed A. Althobaiti; Ola Ali; Mona I. Abdel Ati (Tissue and Cell, 2026)

Lightweight relative map-matching with slope-aware multi-level ground constraints for accurate and robust urban localization - Mahmoud Adham; Yaxin Li; Mostafa Mahmoud; Ahmed Mansour; Wu Chen (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

From waste to worth: A bio-inspired green route for the fabrication of yucca leaf–TiO2 nanocomposites toward efficient and sustainable water purification - Sayed Kotb Ali; Mostafa M. Emara; Rabie Saad Farag; Moaz M. Abdou; Mahmoud F. Mubarak (Environmental Nanotechnology, Monitoring & Management, 2026)

Thermal Decomposition Route for Synthesis of Pure-Phase Zirconium Dioxide Nanocrystals and their Application in the Sorption of Molybdenum Ions in Nitric Acid Solution - Mostafa M. Hamed; Mahmoud M. S. Ali; Refaat F. Aglan (Water, Air, & Soil Pollution, 2026)
For the first time, pure monoclinic ZrO₂ nanocrystals were successfully synthesized via a simple, one-step, and surfactant-free thermal decomposition method using a single precursor compound. In this synthesis, no chemical additives were used; only the metal–organic precursor was employed. This one-step synthesis is notable for its environmental friendliness, low cost, and scalability. Pure-monoclinic structured ZrO 2 has been synthesized in a one step and for the first time applied as an adsorbent to remove molybdenum ions from 3.0 M HNO 3 solution. The nano-oxide was characterized by XRD, SEM, TEM, FTIR, and TGA/DTA to evaluate its structure, morphology, functional groups, and thermal stability. Synthesized ZrO 2 nanocrystals have a pure-monoclinic phase with an average particle size ranging from 14 to 28 nm. To evaluate its performance in radioactive waste treatment, the sorption capacity of pure monoclinic nano-zirconium oxide (Pm-ZrO₂) was investigated for the removal of Mo(VI) from simulated high-level liquid radioactive waste (3.0 M HNO 3 ). The equilibrium sorption behavior of Mo(VI) on Pm-ZrO₂ was evaluated using Langmuir, Freundlich, and Dubinin–Radushkevich isotherm models, whereas the kinetic analysis was conducted based on pseudo-first-order, pseudo-second-order, and intraparticle diffusion models. Kinetic analysis indicated that the sorption process is best described by the pseudo-second-order model, implying that chemisorption is likely the rate-controlling mechanism. The equilibrium sorption isotherm of Mo(VI) onto Pm-ZrO₂ was best represented by the Langmuir and Dubinin–Radushkevich models, suggesting monolayer adsorption occurring on a uniform surface. The maximum equilibrium sorption capacity was found to be 66.70 mg/g, confirming the promising potential of Pm-ZrO₂ as an efficient adsorbent for Mo(VI) removal from acidic radioactive media. Graphical Abstract

Impact of carbon ink on papyrus mechanical and chemical characteristics during accelerated aging: an experimental investigation - Bataa S. M. Mazen; Mohamed Z. M. Salem; Mostafa Abdel-Hamied; Badawi M. Ismail; Mahmoud Ali; Wael S. Mohamed; Rushdya R. A. Hassan (Rendiconti Lincei. Scienze Fisiche e Naturali, 2026)

Delineating Groundwater Aquifers and Subsurface Structures Using Geophysical Data in the Northwestern Part of Minia, Egypt - Sultan A. S. Araffa; Mohamed H. Farag; Mostafa G. Hegab; Mahmoud M. Khalil (Pure and Applied Geophysics, 2026)

Retraction Note: Protective effect of cerium oxide nanoparticles on cisplatin and oxaliplatin primary toxicities in male albino rats - Amira Mohamed Abdelhamid; Shireen Sami Mahmoud; Aziza E. Abdelrahman; Nelly Mohamed Said; Mostafa Toam; Walaa Samy; Marwa AbdEl-Moniem Amer (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Modulation of mTOR, NLRP3, and Nrf2/HO-1 signaling by atorvastatin and nitazoxanide in experimental ulcerative colitis - Hayam Ali AlRasheed; Mahmoud S. Abdallah; Esraa M. Mosalam; Mostafa M. Bahaa; Muhammed M. Salahuddin; Amir O. Hamouda; Sarah Alrubia; Amsha S. Alsegiani; Eman El-Khateeb; Mohamed Kh. Elmahdy; Nora Elshorbagi; Abd El Razeq A. Meselhy; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Sugarcane Yield Estimation at Field Scale Using Time Series Data from LANDSAT 7 - Mostafa Khosravirad; Mahmoud Omid; Fereydoun Sarmadian; Soleiman Hosseinpour; Hassan Ghasemi-Mobtaker (Journal of the Indian Society of Remote Sensing, 2026)

Engineered Spray-Dried PLGA-PEG Dual-Coated Micelles with Lactose/Trehalose Matrices for Pulmonary Doxorubicin Delivery: Achieving Sustained Release and Improved Aerosol Performance in NSCLC Therapy - Randa Mohammed Zaki; Alaa Ayman; Eman Mostafa Samy; Mahmoud Mohamed Omar; Obaid Afzal; Rawan Bafail; Waad A. Samman; Omiya A. Hasan (Journal of Pharmaceutical Innovation, 2026)

Advanced lipid-based niosomes for enhanced transdermal delivery of olmesartan medoxomil via intracutaneous drug depot: a novel biomimicry approach - Shahinaze A. Fouad; Mostafa I. Gebril; Fathy I. Abd Allah; Mahmoud H. Teaima; Mohamed El-Nabarawi; Mohammed Elmowafy; Omnia M. Sarhan (Drug Delivery and Translational Research, 2026)

Survival and renal outcomes of mucormycosis infection and its treatment regimens in resource-limited settings: a retrospective case series - Mahmoud Gamal Algammal; Mohamed R. S. B. Elgmmal; Abdelrahman Mohamed Yassein Abbas; Mohammed Mostafa Mohammed Marouf; Ahmed Mohamed Saleh; Mostafa M. Bahaa; Khlood Mohammad Aldossary; Mostafa Mahmoud Mohamed Ali; Marwa Kamal (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Pesticide residues in imported black tea in Egypt: Occurrence, processing-induced reduction, and health risk assessment - Ahmed Elmahdy; Hend Mahmoud; Mostafa Soliman; Ahmed Bakr; Abdulrhman Gamal; Fawzy Eissa (Food Chemistry, 2026)

Ultrasound-induced ternary composite system for off-flavor reduction in thermally processed egg white proteins - Mohamed Salama; Mostafa Gouda; Mahmoud Abou-Elsoud; Xiaomeng Li; Long Sheng; Zhaoxia Cai (Food Chemistry, 2026)

The protective effect of ambroxol against cyclophosphamide-induced acute kidney injury involves Nrf2/HO-1 signaling upregulation and suppression of oxidative and inflammatory damage - Reem S. Alruhaimi; Emad H. M. Hassanein; Sulaiman M. Alnasser; Hanan S. Althagafy; Mostafa Sabry; Abdullatif A. Ahmed; Ayman M. Mahmoud (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Protective role of S-carboxymethylcysteine against cyclophosphamide nephrotoxicity: involvement of Nrf2/HO-1 signaling and suppression of oxidative stress, inflammation, and apoptosis - Reem S. Alruhaimi; Emad H. M. Hassanein; Sulaiman M. Alnasser; Ahmad F. Ahmeda; Hanan S. Althagafy; Mostafa Sabry; Abdullatif A. Ahmed; Ayman M. Mahmoud (Molecular & Cellular Toxicology, 2026)

Rosuvastatin-Loaded Glycerosomes as a Neuroprotective Strategy Against Hyperlipidemia-Induced Brain Dysfunction: Development, Optimization, and in vivo Evaluation - Mahran Mohamed Abd El-Emam; Mohamed Ibrahim; Milad Reda Qelliny; Mahmoud Mostafa; Marwa Mohamed El Sayed; Maha S. Kilany; Amira Ebrahim Alsemeh; Rania Said Moawad; Mohamed Fouad Mansour (Journal of Pharmaceutical Innovation, 2026)
Objective Brain injury and neurodegenerative conditions are largely caused by oxidative damage and endoplasmic reticulum (ER) stress spurred on by hyperlipidemia. To lessen these consequences in the brains of hyperlipidemic rats, this study assesses the therapeutic potential of both rosuvastatin glycerosomes (RSV GLSMs) and niacin. Methods The study had five groups: control, hyperlipidemia induced by poloxamer 407 (P407), RSV GLSMs, niacin, or a combination of RSV GLSMs and niacin. Serum samples were collected for lipid profile assessment, whereas brain tissues were harvested for Reverse Transcription Polymerase Chain Reaction, histopathological, and immunohistochemical analyses. Results The treatment of P407 significantly decreased high-density lipoprotein and increased serum triglycerides, although RSV GLSMs and niacin substantially mitigated these changes. Malondialdehyde also surged in P407 rats, and total antioxidant capacity was diminished. RSV GLSMs and niacin supplementation significantly improved antioxidative defenses, with the combination therapy exhibiting more pronounced effects. RSV GLSMs and niacin notably lessen ER stress–responsive gene expression, including Eukaryotic Initiation Factor 2 alpha (eIF2α), C/EBP Homologous Protein (CHOP), X-box Binding Protein 1 (XBP1), c-Jun N-terminal Kinase (JNK), Binding Immunoglobulin Protein (BIP), and Activating Transcription Factor 6 (ATF-6) levels. In addition, RSV GLSMs and niacin improved autophagy by downregulating the Mammalian Target of Rapamycin (mTOR) and p62, and upregulating Beclin1 and Microtubule-associated protein 1A/1B-light chain 3, type II (LC3-II). According to immunohistochemical findings, RSV GLSMs and niacin reduced reactive gliosis and modulated the expression of B-cell lymphoma 2/Bcl-2-associated X protein (Bcl-2/Bax). Histopathological findings exhibited improved brain morphology, reduced vacuolization, and normalized glial cell distribution in the RSV GLSMs and niacin combination group, closely resembling the control group. Conclusions Overall, RSV GLSMs and niacin effectively mitigate hyperlipidemia-induced brain damage by modulating oxidative stress, ER stress, and autophagy pathways, suggesting potential as a promising treatment strategy.

Ulcerative colitis, pathophysiological mechanisms and drug repurposing: a new therapeutic dawn-narrative review - Mostafa M. Bahaa; Mahmoud S. Abdallah; Esraa M. Mosalam; Ahmed R. Gardouh; Mahmoud Nazih; Eman Hamza; Reham Abdullah Al-Dhelaan; Noha Kamal (Inflammopharmacology, 2026)

Attenuation of inflammatory response via Corchorus olitorius seeds-derived Penicillium sp. metabolites in immunocompromised rats - Arwa Mortada Ahmed; Mohamed Hisham; Reham H. Mohyeldin; Sherif A. Maher; Omar. Y. Tammam; Ramadan Yahia; Nehad M. Reda Abdel-Maqsoud; Mahmoud A. Elrehany; Basma Khalaf Mahmoud; Usama Ramadan Abdelmohsen; Mostafa A. Fouad (Natural Product Research, 2026)

Intrarectal delivery of chitosan hydrogel-encapsulated mesenchymal stem cell-conditioned media attenuates disease severity in experimental ulcerative colitis - Hossein Mokhtari; Mostafa Haji Molla Hoseini; Seyed Mahmoud Hashemi; Shadi Tahvildari; Farshid Yeganeh (Inflammopharmacology, 2026)

Quantum-Inspired Hybrid Bald Eagle-Ukari Algorithm with Reinforcement Learning for cybersecurity optimization in smart aquaculture systems: A novel bio-inspired intrusion detection and prevention framework - Wael Said; Mohssen Elbagory; Faizah Amer Altihani; Ibrahim Mohamed; Mahmoud El-Sharkawy; Ashwaq M. Alnemari; Farahat S. Moghanm; Mostafa Elbaz (Aquacultural Engineering, 2026)

Atorvastatin ameliorates cerebral cortical pathological and cognitive alterations in aged rats: Histological & immunohistochemical study - Mohamed Elshafey; Hany K.K. Mostafa; Mosaab Salah El-din El-Agawy; Marwa Mohamed Safwat; Mohamed El-Sherbiny; Hasnaa Ali Ebrahim; Raja El Hasnaoui-Saadani; Nehal M. Elsherbiny; Mohamed Abomosallam; Ateya M. Ibrahim; Ehab Kamal Ali; Zeinab A. Ali; et al. (Tissue and Cell, 2026)

Ultrasound-assisted xylitol conjugation improves heat resistance of egg white-casein complexes for food colloidal applications - Mohamed Salama; Mostafa Gouda; Mahmoud Abou-Elsoud; Xiaomeng Li; Sadaqat Ali; Long Sheng; Zhaoxia Cai (Food Hydrocolloids, 2026)

Efficacy of butylated hydroxytoluene nanoparticles in enhancing the quality and preservation of stallion chilled semen - Wael A. Khalil; Hesham E. Mostafa; Mohamed K. Derbala; Mohammed A. Alfattah; Waleed Alhujaili; Mahmoud A. E. Hassan; Mostafa A. El-Harairy; Sameh A. Abdelnour (Veterinary Research Communications, 2026)

Natural products as HMG-CoA reductase inhibitors (statins) for the management of non-communicable diseases - Radwa N. Muhammad; Nora M. Aborehab; Shaza H. Aly; Noha N. Nasr; Merhan O. Hindam; Aya M. Mustafa; Safaa A. Faheem; Mariam H. Fawzy; Mohammed E. Abo-El Fetoh; Ahmed M. El-Dessouki; Mostafa A. Rabie; Riham A. El-Shiekh; et al. (Inflammopharmacology, 2026)
Non-communicable diseases, such as diabetes, cancer, as well as cardiovascular, metabolic, and central nervous system disorders stand for significant global health burden. Statins, as HMG-CoA reductase inhibitors, have emerged as a basis in the management of hypercholesterolemia and the prevention of cardiovascular disorders. In this review, we summarize the role of statins in a variety of pathologies, ranging from their well-recognized effects in cardiovascular disorders, to the newly revealed favorable effects in cancer, eye, autoimmune, kidney, gastrointestinal, bone, and autoimmune disorders. Additionally, the current review explores insights into the potential role of natural products as HMG-CoA reductase inhibitors. Future research should focus on the synergistic effects of natural therapies with synthetic statins to improve health outcomes in populations burdened by non-communicable diseases.

Alteplase versus tenecteplase in acute ischemic stroke with large vessel occlusion: a systematic review and meta-analysis - Mostafa Hossam El Din Moawad; Ibrahim Serag; Ahmed A. Abo Elnaga; Dina Essam Abo-elnour; Hamza A. Abdul-Hafez; Mohamed Ahmed Hammad; Lobna Ahmed Mohamed; Rawan Kamal Mohamed; Amir N. Attia; Abdelaziz A. Awad; Ibraheem M. Alkhawaldeh; Mahmoud Hegazy; et al. (European Journal of Clinical Pharmacology, 2026)

Optimization of UHPC with basil plant ash: Impacts on strength, durability, and gamma-ray attenuation - Sahar A. Mostafa; Islam N.Fathy; Alaa A. Mahmoud; Mohamed A. Abouelnour; K.A. Mahmoud; Shaaban M. Shaaban; Sameh A. Elhameed; Islam M. Nabil (Annals of Nuclear Energy, 2026)

Nanocapsule-based vitamin B12 as a novel strategy against vancomycin-induced nephrotoxicity: Targeting oxidative stress, ER stress, inflammation, and fibrosis in rats - Mahran Mohamed Abd El-Emam; Maha S. Kilany; Mohamed Ibrahim; Milad Reda Qelliny; Mahmoud Mostafa; Marwa Mohamed El Sayed; Tarek khamis; Rasha Ahmed Ahmed Agaga; Asmaa Monir Eltaweel; Mohamed Fouad Mansour (Toxicology and Applied Pharmacology, 2026)

The neonicotinoid Imidacloprid provokes Ferritinophagy/Ferroptosis Axis disruption in rats' liver: The attenuation impact of Berberine chloride-loaded nano-liposomes - Amina A. Farag; Marwa Kamal; Heba S. Youssef; Ashraf Mohamed Sadek; Amira M. Badr; Mahmoud Mostafa; Reham M. Abdelfatah; Shaimaa E. Radwaan; Eman Kamel Mohamed Khalfallah; Nashwa Nabil; Nashwa E. Ahmed; Hesham Mohamed Elwakeel; et al. (Toxicology and Applied Pharmacology, 2026)

Oil sludge from an environmentally hazardous pollutant to an efficient source for energy production via thermal/ catalytic pyrolysis routes - Mohamed N.A. Mahmoud; Esraa M. El-Fawal; Ahmed M.A. El Naggar; Asmaa I. Zahran; Hussien A. El Sayed; Islam M. El-Sewify; Bassem H. Heakal; Mostafa M.H. Khalil (Fuel, 2026)

Genetic characterization of highly pathogenic avian influenza A/H5N8 virus isolated from commercial poultry farms in Egypt reveals zoonotic potential - Nahed M. Bedair; Moustafa A. Sakr; Ahmed Mourad; Nourhan Eissa; Omaima Khamiss; Mahmoud M. Naguib; Ahmed Mostafa (Archives of Virology, 2026)

Enhanced Oil/Water Separation Performance of Asymmetric PVDF-PLA/MXene Composite Membranes - Zainab Mahmoud Abdel Mejeed; K. R. Riyamol; Swathi Yempally; Mostafa H. Sliem; Deepalekshmi Ponnamma (Water Conservation Science and Engineering, 2025)
In this study, functionally asymmetric Janus-type membranes were developed using polyvinylidene fluoride (PVDF) and polylactic acid (PLA) polymers through electrospinning with one layer deposited over the other, to create an effective oil-water emulsion separation membrane. To enhance the membrane properties, MXene was synthesized from the MAX phase and incorporated into the PLA solution. During the electrospinning process, PLA-MXene solutions of varying compositions were spun over the PVDF base layer to fabricate the composite membranes. The separation efficiency of the PVDF-PLA/Mxene composite membranes was evaluated and compared to that of the neat PVDF-PLA membrane. Among the modified membranes, the 2 wt% Mxene-reinforced composite demonstrated the highest separation efficiency of 86.79%, followed by the 1 wt% Mxene composite at 80.24%, compared with 75.76% for the neat PVDF-PLA membrane. The increased capacity of the Mxene-reinforced membranes to remove organic pollutants from the solution indicates their superior performance.

Exploring the Efficacy and Safety of Argatroban as an Adjunct to Antiplatelet Therapy in Ischemic Stroke Patients: A Systematic Review and Meta-analysis - Yousr Ahmed; Mostafa Hossam El Din Moawad; Gulnaz Bahtiyarova; Younes Nabgouri; Mohammed Elkholy; Reham M. Wagih; Ibrahim Serag; Ibraheem M. Alkhawaldeh; Mohamed Abouzid; Mahmoud Elsayed (Translational Stroke Research, 2025)

Effect of casting joint position on structural behavior of beams by HSC and SCHSC: experimental and numerical analysis - Mostafa S. Rizk; Nour Bassim Frahat; Islam Salama; Mahmoud H. Abd-Elrahman; Ibrahim Saad Agwa (Innovative Infrastructure Solutions, 2025)
High-strength concrete (HSC) and self-compacting high-strength concrete (SCHSC) are increasingly used in modern construction. This study investigates the effect of different construction joint positions on their mechanical properties and structural behavior. Understanding the influence of joint orientation and location is essential for ensuring the safety and durability of structural elements. Therefore, studying construction joints is crucial for improving design guidelines and optimizing construction practices. In HSC, joints were placed at 0°, 45°, and 90° at midspan and horizontally at mid-height, while in SCHSC, they were located horizontally at 0%, 25%, 50%, and 75% of the specimen height. Experimental tests on compressive strength, splitting tensile strength, and load–deflection response were performed alongside numerical analysis using Abaqus. Results showed that construction joints reduced the load capacity of HSC beams by 13.02% (horizontal) and 17.56% (angled), and of SCHSC beams by 6.70%, 11.22%, and 17.38% at 75%, 50%, and 25% heights, respectively. Finite element models demonstrated close agreement with experiments, with discrepancies below 6.3%. The study provides new insights into the structural performance of HSC and SCHSC beams with construction joints.

Eco-friendly solutions: a comprehensive review of natural coagulants for sustainable water treatment - Sayed Kotb Ali; Moaz M. Abdou; Mostafa M. Emara; Rabie Saad Farag; Mahmoud F. Mubarak (Environmental Geochemistry and Health, 2025)
Water pollution and scarcity are escalating global challenges that necessitate the development of sustainable water treatment technologies. Coagulation-flocculation, a crucial method for water purification, has traditionally relied on chemical coagulants such as alum and ferric chloride. However, these chemical treatments are associated with significant drawbacks, including the generation of toxic sludge, disruption of water pH, high operational costs, and adverse environmental impacts. In response to these issues, natural coagulants derived from plants, animals, and microorganisms have emerged as promising eco-friendly alternatives. This review explores the mechanisms, applications, and environmental advantages of natural coagulants in water treatment. Studies demonstrate their effectiveness in removing turbidity, heavy metals, pathogens, and other pollutants from both surface and synthetic wastewater. Compared to chemical coagulants, natural alternatives produce less sludge, are less toxic, and offer a more sustainable and environmentally friendly solution to water treatment. However, challenges persist, particularly in terms of scalability, standardization, and cost-effectiveness. The performance of natural coagulants can vary depending on geographical origin, and the lack of standardized extraction methods hinders their large-scale application. Future research should focus on optimizing extraction processes, addressing scalability issues, and exploring hybrid systems that combine the benefits of both natural and chemical coagulants. The continued development of natural coagulants holds great promise for creating more sustainable, cost-effective, and environmentally friendly water treatment solutions. Graphical Abstract

Enhanced photocatalytic performance of Ag-doped CuWO₄ thin films prepared by chemical spray pyrolysis - Mohammed M. Gomaa; Mahmoud S. Abdel-Wahed; Mostafa Boshta; Mohamed H. Sayed (Environmental Science and Pollution Research, 2025)

Utilizing Hot-Melt Extrusion and Spray Drying Techniques for Preparation of Liquid and Solid Cannabidiol Nano-Structured Lipid Carriers Formulations - Iman E. Taha; Mahmoud A. ElSohly; Nourhan Mostafa; Mashan Almutairi; Eman A. Ashour (AAPS PharmSciTech, 2025)
Nanostructured lipid carriers (NLCs) have attracted considerable interest as drug delivery systems capable of enhancing the solubility and oral bioavailability of poorly water-soluble drugs. In our previous work, cannabidiol (CBD)-loaded NLCs prepared by hot homogenization demonstrated improved dissolution and oral bioavailability. In the present study, hot-melt extrusion (HME) was investigated as a rapid and easily scalable alternative method for the preparation of CBD NLCs. Additionally, spray drying was used to convert the prepared CBD NLCs into a solid dosage form. CBD NLCs were prepared using HME at different screw speeds (100, 200, and 300 rpm), followed by probe sonication, and characterized for particle size, entrapment efficiency (EE), and drug release. Spray drying was performed with different carriers (D-lactose, Kollidon® VA 64, maltodextrin 12, and Soluplus®) to evaluate their compatibility and performance. The results showed that the screw speed has an impact on the properties of the NLCs, while probe sonication further reduced particle size, resulting in enhanced entrapment efficiency, and drug release of all formulations. Although NLC produced at a screw speed of 300 rpm was the most stable in both 4 °C and 25 °C. Among the carriers tested for spray drying, maltodextrin achieved nearly complete CBD release, while Soluplus® led to increased particle size and reduced release. Overall, HME combined with probe sonication proved to be a robust approach for the preparation of CBD NLCs, which were successfully converted into solid powder formulations by spray drying, offering a promising strategy for scalable production of CBD NLCs. Graphical Abstract

Magnetic ternary nanocomposite from ultra-purified metakaolin for radioactive decontamination: sorption mechanisms and practical implications - Mohamed Ragheb El-Naggar; Yanhui Dong; Mostafa Mohamed Hamed; Emad Hassan Borai; Abdelghany El Abd; Hager Hosny Ibrahiem; Mahmoud Mahfouz Gouda; Muhammad Sabry Mansy; Amer Mahmoud Amer Hassan; Rehab Osman Abdel Rahman (Environmental Science and Pollution Research, 2025)

Photocatalytic oxidation of ammonia using copper-mediated phosphotungstic acid intercalated sulfonated bentonite for sustainable eutrophication control: A case study from Lake Qarun - Mostafa Gaber Refaai; Hassan A. Rudayni; Ahmed A. Allam; Mostafa R. Abukhadra; Mahmoud S.M. Abdel Wahed (Environmental Research, 2025)

Synergistic effects and mechanisms of ultrasonic, pH, and peracetic acid pretreatment on sludge anaerobic fermentation to stimulate short-chain fatty acid production - Eid S. Gaballah; Lei Gao; Richen Lin; Mahmoud M. Ali; Biao Yang; Mostafa Sobhi; Chongpeng Tang; Guangcan Zhu (Bioresource Technology, 2025)

The effect of celery (Apium graveolens) seed powder in the diet on growth, immune function, antioxidant status and gut microbial balance in broiler chickens - Mohamed H. Negm; Ahmed K. Aldhalmi; Elwy A. Ashour; Laila A. Mohamed; Islam M. Youssef; Mahmoud Moustafa; Mostafa I. Abdelglil; Seham Abdel-Shafi; Samir A. Mahgoub; Mohamed E. Abd El-Hack; Ayman A. Swelum (Tropical Animal Health and Production, 2025)

Microalgae as a source of carotenoids in foods, obstacles and solutions - Heba Sayed Mostafa; Marwa Mahmoud Hashem (Phytochemistry Reviews, 2025)
Recently, microalgae have attracted attention as a natural source of healthier bioactive molecules, especially carotenoids, because human bodies lack the ability to synthesize them, and their intake is necessary for human nutrition. Microalgae can produce various classes of these natural products, distinguished by their health benefits. In food sectors, microalgae are available as whole cells or as a source for extracting a specific carotenoid. This review summarizes recent knowledge of the biosynthesis pathway and the factors affecting carotenoid content, as well as strategies for increasing microalgae synthesis of various carotenoids. New uses of carotenoid-rich microalgae in food are highlighted, along with the main challenges and suggested solutions for using microalgal-carotenoids in the foodstuff. Carotenoids, particularly β-carotene and astaxanthin, face significant challenges in terms of bioavailability and stability when included in foods. Although many solutions were proposed, more research is required to determine the stability of other carotenoids under various food processing techniques. Furthermore, future studies should focus on improving bioavailability and accessibility after digestion in order to benefit from all added carotenoids. Modern technology and a fast-paced lifestyle necessitate the inclusion and acceptance of microalgal carotenoids, particularly for the most vulnerable populations, children, and pregnant women.

Cerebellar transcranial magnetic stimulation in essential tremor: a systematic review and meta-analysis of safety and efficacy - Abdallah Abbas; Mohamed Abouzid; Haneen Sabet; Ahmed Mansour; Abdelfattah Arafa; Ahmed Elshahat; Ahmed Mostafa Amin; Mahmoud Tarek Hefnawy; Mohamed El-Moslemani; Amna Hussein; Mostafa Hossam El Din Moawad; Shereen M. Olama; et al. (Acta Neurologica Belgica, 2025)

Pesticide residues in Green, roasted, and capsule coffee from the Egyptian market: Occurrence, processing effects, and health risk assessment - Abdulrhman Gamal; Mohamed Abdel-Megeed; Hend Mahmoud; Mostafa Soliman; Mohamed Al-Anany; Fawzy Eissa (Food Chemistry, 2025)

The effects of flavonoid baicalein on miRNA expressions in cancer: a systematic review - Mohanna Khandan; Mohammad Amin Khazeei Tabari; Seyed Mostafa Rahimi; Mahmoud Hassani; Abouzar Bagheri (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Comparison between clopidogrel and ticagrelor in CYP2C19 loss-of-function alleles coronary artery disease and stroke patients: a meta-analysis - Mahmoud Elsayed; Mostafa Hossam El Din Moawad; Mohammed Elkholy; Yousr Ahmed; Younes Nabgouri; Gulnaz Bahtiyarova; Ibraheem M. Alkhawaldeh; Mohamed Abouzid; Reham M. Wagih (European Journal of Clinical Pharmacology, 2025)

Sucrose esters of aryldihydronaphthalene-type lignans, and antitumor activity of extracts of Moltkiopsis ciliata (Forssk.) aerial parts - Amal Mahmoud Youssef Moustafa; Mohamed Abdel-Moneim; Mohamed E. Mostafa; Mamdouh Abdel-Mogib; Marwa Rabee Abdel-Hak (Natural Product Research, 2025)

The growth performance, feed efficiency, intestinal histo-morphological indices, antioxidat ive status, and related genes of Nile tilapia (Oreochromis niloticus) fed fermented rice hulls - Mohamed S. El-Ghafloul; Mostafa A. Ibrahim; Ibrahim M. Abd El-Razek; Safaa E. Abdo; Asem A. Amer; Amr I. Zaineldin; Mahmoud S. Gewaily; Mahmoud A.O. Dawood (Aquaculture, 2025)

The cryoprotective effects of celastrol nanoemulsion on post-thawed attributes and fertilizing ability of cryopreserved buffalo semen - Wael A. Khalil; Salwa A. Elkhamy; Mohamed M. Hegazy; Mahmoud A. E. Hassan; Sameh A. Abdelnour; Mostafa A. El-Harairy (Veterinary Research Communications, 2025)
Celastrol (CL), a natural molecule isolated from Tripterygium wilfordii Hook. f., possesses notable therapeutic potential across a range of disease states. However, its impact on semen quality following cryopreservation has not been extensively investigated. Thus, this research comprehensively evaluated the cryoprotective effects of celastrol nanoemulsion (CNE) on buffalo semen by analyzing sperm quality, sperm kinematics, acrosome status, oxidative stress, mitochondrial membrane potential, ultrastructure, microbiota, and apoptotic-like changes. Semen samples (n = 45) were collected from five buffalo bulls and subjected to cryopreservation following a standard procedure. Prior to freezing, Tris-extenders were supplemented with celastrol nanoemulsion (CNE) at concentrations of 0 (CNE0), 25 (CNE25), 50 (CNE50), 100 (CNE100), and 200 (CNE200) µg/mL. The results showed that CNE supplementation (excluding 200 µg/mL) significantly improved sperm progressive motility, viability, and membrane integrity in post-thawed samples and after 2 h of incubation at 37 °C with 5% CO 2 . Specifically, sperm kinematic parameters were significantly improved by 50 and 100 µg/mL CNE compared to other treatments ( P < 0.05). Furthermore, a superior percentage of sperm with intact acrosomes was remarked in the 25, 50, and 100 µg/mL CNE groups than in the other groups ( P < 0.001). Total antioxidant capacity (TAC) was significantly higher in the CNE100 group compared to the CNE0 group ( P < 0.001), while no significant differences were found between CNE100 and the other treated groups ( P > 0.05). Oxidative stress markers (MDA, NO, and H 2 O 2 ) were significantly lower in CNE50 and CNE100 groups compared to all other treatments ( P < 0.001). Furthermore, the CNE 100 µg/mL group exhibited a higher percentage of viable sperm and a lower percentage of apoptotic sperm than other groups ( P < 0.05). The addition of CNE to the freezing extender significantly reduced the total bacterial count, spore-forming bacteria, and coliform bacteria count in post-thawed buffalo bull sperm ( P < 0.001). Transmission electron microscopy analysis revealed that CNE 100 µg/mL improved and sustained sperm ultrastructure. Notably, the CNE 100 µg/mL treatment also improved the pregnancy rate compared to the control group (82.0% vs. 68.0%). Collectively, the results indicate that CNE at concentrations of 50–100 µg/mL can be effectively used for improving sperm cryo-resistance. This is achieved through improvements in sperm quality and kinematic parameters, attenuation of oxidative stress and microbiota, enhancement of mitochondrial function, preservation of sperm ultrastructure, and improved fertilizing capacity. This study highlights the potential of celastrol nanoemulsion as a nanotechnology-based strategy for optimizing assisted reproductive technologies in livestock.

Association of Epistatic Effects of lncRNA GAS5, miR-146a, IRAK-1, and miR-155 Genetic Variants with Multiple Sclerosis Risk and Severity - Ghada Ayeldeen; Olfat G. Shaker; Mohammed Gomaa; Mostafa M. Magdy; Nourhan Elsamaloty; Ahmed S. Kamel; Mahmoud A. Senousy (Molecular Neurobiology, 2025)
The complex genetic architecture of heritability in multiple sclerosis (MS) remains undisclosed mainly. Epistasis (gene–gene interaction) substantially impacts MS; however, it is largely unexplored, especially among the non-coding RNA genes and their targets. The long non-coding RNA GAS5 exacerbates demyelination and sponges miR - 146a and miR-155 , impeccable contributors to MS pathogenesis. miR - 146a negatively regulates the immune responses by targeting IRAK-1 . We investigated the association of epistatic effects and haplotypes of five single nucleotide polymorphisms (SNPs), GAS5 rs2067079, miR - 146a rs2910164 and rs57095329, IRAK-1 rs3027898, and miR-155 rs767649, with the risk of MS and its phenotypes. The expression quantitative trait locus (eQTL) associated with these variants was explored through bioinformatics analysis. The study enrolled 116 MS patients and 120 healthy controls. No strong linkage disequilibrium ( D ′ ≥ 0.8) was detected among the studied SNPs. SNP-SNP interactions overlaid an overall magnified risk of MS and its phenotypes compared to the single-locus effects. After adjustment for multiple comparisons, the most significant interactions associated with the risk of overall MS and secondary-progressive MS were rs2067079-rs2910164, rs2910164-rs57095329, and rs3027898-rs767649. The last two former SNP-SNP interactions were highly associated with relapsing–remitting MS risk. The same pattern of interactions, as observed in association with MS risk, was female-specific. The CCAAA haplotype (alleles in the order of rs2067079, rs2910164, rs57095329, rs3027898, and rs767649) was protective against MS risk (CCAAA vs. CGAAT, adjusted OR = 0.14, 95% CI = 0.03–0.69, P = 0.009). Among MS patients, harboring the CGACT and CGAAT haplotypes was more prevalent in females and males, respectively. MS patients having EDSS ≥ 6 had a significantly higher frequency of the CCGCA haplotype than those with EDSS < 6. Functional analysis revealed rs2067079, rs57095329, and rs767649 as strong cis-eQTL regulating multiple genes, particularly in the brain and immune system. We propose that a magnified combined effect of GAS5 , miR - 146a , IRAK-1 , and miR - 155 genetic variants via epistatic interactions might impact the risk of MS and its phenotypes and could help in the risk stratification of MS patients.

Rutin-Loaded Nanocapsules Mitigate Vancomycin-Induced Hepatotoxicity: Development, Characterization, Optimization, and In Vivo Evaluation - Mohamed Ibrahim; Mohamed Fouad Mansour; Mahran Mohamed Abd El-Emam; Tarek khamis; Maha S. Kilany; Amira Ebrahim Alsemeh; Asmaa Monir Eltaweel; Milad Reda Qelliny; Mahmoud Mostafa; Marwa Mohamed El Sayed (Journal of Pharmaceutical Innovation, 2025)
Background Vancomycin (VCM)-induced hepatotoxicity is a significant clinical concern due to its association with oxidative stress, apoptosis, and inflammatory responses. This study investigated the formulation and potential preclinical application of rutin-loaded nanocapsules (RUT-NC) as a hepatoprotective agent against VCM-induced liver injury. Methods Hepatotoxicity was induced in rats through VCM administration, followed by oral treatment with RUT-NC. Liver function, oxidative stress markers, apoptotic proteins, lipid metabolism regulators, and inflammatory cytokines were subsequently evaluated. Results RUT-NC treatment significantly improved liver function parameters, attenuated oxidative stress, and modulated apoptotic pathways by downregulating the expression of p38 , p53 , caspase-8 , miR-122 , miR-7 , and beclin-1. Furthermore, RUT-NC restored lipid metabolism homeostasis by regulating the expression of PPAR-α, FASN, and SREBP-1. Notably, it exerted potent anti-inflammatory effects by suppressing NF-κB , TNF-α , IL-1β , IL-6 , IL-17 , and Gasdermin-D , thereby mitigating chronic liver inflammation. The pathological effects of VCM administration on hepatocytes were effectively counteracted by RUT-NC. Conclusion RUT-NC demonstrates promising hepatoprotective properties by enhancing antioxidant defenses, inhibiting apoptosis, regulating lipid metabolism, and reducing inflammation. These findings highlight its potential as a therapeutic intervention for drug-induced liver injury (DILI) and warrant further investigation for clinical application.

Oxadiazole-Based Fluorescent Dyes: Photophysical Characterization and Dual Application in Latent Fingerprint Detection and Security Inks - Safa A. Badawy; Abdullah I. Kamel; Ahmed E. Soliman; Mostafa M. Abdul Wahab; Anas M. Khader; Mahmoud E. Abdelgawad; Elaria A. Ibrahim; Basant A. Mostafa; Karim M. Elmezain; Mohamed R. Elmorsy (Journal of Fluorescence, 2025)
In this study, a series of novel oxadiazole-based fluorescent dyes were synthesized and thoroughly characterized through spectroscopic analysis, theoretical modeling, and application testing. The structural design incorporated donor–acceptor motifs to promote intramolecular charge transfer (ICT), resulting in strong fluorescence across the violet-to-green spectral region (363–536 nm) with large Stokes shifts. The photophysical behavior of the dyes was investigated in solvents of varying polarity, revealing distinct solvatochromic effects and enhanced emission efficiency, particularly for diphenylamine-substituted derivatives. Density Functional Theory (DFT) calculations supported experimental observations, confirming frontier orbital distributions consistent with ICT. Thermal stability was confirmed via thermogravimetric analysis, with decomposition temperatures exceeding 250 °C. To explore practical utility, the most emissive dyes were successfully embedded into oxadiazole-based microparticles and tested for latent fingerprint development on porous and non-porous surfaces. Additionally, water-based ink formulations prepared from these dyes demonstrated excellent stability and visibility under UV light, making them suitable for covert writing and anti-counterfeiting applications. The combined structural, optical, and application-oriented results highlight the potential of these oxadiazole derivatives as multifunctional fluorescent materials for forensic and security technologies.

Overcoming challenges in the analysis of the ubiquitous emerging contaminant trifluoroacetic acid employing trap column liquid chromatography tandem mass spectrometry - Ramadan Sayed; Ahmed A. Omran; Rabie S. Farag; Hend A. Mahmoud; Mostafa Soliman (Journal of Hazardous Materials, 2025)

Insight into dairy casein implications that enhance egg white proteins' thermodynamic and microrheological functions - Mohamed Salama; Mostafa Gouda; Mahmoud Abou-Elsoud; Dewei Shu; Xiaomeng Li; Long Sheng; Zhaoxia Cai (Food Chemistry, 2025)

Disclosing the impact of metformin and methotrexate in adjuvant arthritis in female rats: molecular docking and biochemical insights on visfatin - Ahmed Mostafa Mahmoud; Esam Mohamed Abu Alfadl; Ahmed R. H. Ahmed; Azza M. A. Abouelella; Omar Alshazly; Mamdouh F. A. Mohamed; Hasan El Allaf; Rasha M. Allam (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Pentoxifylline uses in inner ear diseases - Ahmed Ramzi; Subhia Maya; Nadeen Balousha; Mufreh Amin; Rovan Ahmed Rouby; Ghalia Aljarrah; Dalia Gamal Elnady; Ahmed Samir; Thoria Ibrahim Essa Ghanm; Zahraa Natheer Bhaya; Abdallah Altarras; Fares Abdelsalam; et al. (European Journal of Clinical Pharmacology, 2025)

Targeting TLR4/NF-κB signaling, oxidative stress, and apoptosis by farnesol mitigates cadmium-induced testicular toxicity in rats - Emad H.M. Hassanein; Mohammed F. Alotaibi; Reem S. Alruhaimi; Mostafa Sabry; Ghadir A. Sayed; Ahmed M. Atwa; Ayman M. Mahmoud (Tissue and Cell, 2025)

Quercetin-loaded PEGylated liposomes alleviate testicular dysfunction in alloxan-induced diabetic rats: The role of Kisspeptin/Neurokinin B/Dynorphin pathway - Mohamed Fouad Mansour; Amany Behairy; Mahmoud Mostafa; Tarek Khamis; Amira Ebrahim Alsemeh; Noura Mohammed Qenawy Ahmed; Mahran Mohamed Abd El-Emam (Toxicology and Applied Pharmacology, 2025)

Combined Effects of Yellow Mealworm (Tenebrio molitor) and Saccharomyces cerevisiae on the Growth Performance, Feed Utilization Intestinal Health, and Blood Biomarkers of Nile Tilapia (Oreochromis niloticus) Fed Fish Meal-Free Diets - Ehab M. Anany; Mostafa A. Ibrahim; Ibrahim M. Abd El-Razek; El-Said M. El-Nabawy; Asem A. Amer; Amr I. Zaineldin; Mahmoud S. Gewaily; Mahmoud A. O. Dawood (Probiotics and Antimicrobial Proteins, 2025)
Aquafeed quality is the most critical factor for aquaculture sustainability. However, limitations of traditional feed ingredients such as fishmeal (FM) need alternative strategies to ensure the nutritional requirements for aquatic animals. In this trial, four test diets were formulated (2 × 2 factorial design), where FM was incorporated in two diets at 10% with or without Saccharomyces cerevisiae (SC) at 1 g/kg. At the same time, FM was replaced with yellow mealworm ( Tenebrio molitor ) meal (TM) with or without SC at 1 g/kg. The growth performance indices (final weight, weight gain, and SGR), and the feed utilization indices (FCR and PER) were markedly affected by the protein source (FM or TM) and dietary SC ( P < 0.05). The protein source (FM or TM) significantly ( P < 0.05) affected the whole-body protein and lipid contents, while the moisture and ash contents were unaffected ( P > 0.05) by TM or SC. The growth of the intestinal villi showed a marked increase in both height and branching in the treated groups with SC along the whole length of the intestine. Furthermore, the immune cell infiltration was prominent near the intestinal crypts of the middle intestinal segments in the supplemented groups by SC. Dietary TM and SC revealed improved hepatic parenchyma in the liver tissue better than other groups. The hematological indices, including hemoglobulin, hematocrit, red blood cells, and white blood cells, were markedly affected by dietary SC ( P < 0.05). The lysozyme activity and phagocytic index were markedly affected by dietary SC, while phagocytic activity was affected by dietary TM ( P < 0.05). The catalase, glutathione peroxidase, and malondialdehyde were markedly affected by the interaction between dietary protein source and SC, while superoxide dismutase was affected by dietary SC ( P < 0.05). In conclusion, adding SC could enhance the utilization of TM by Nile tilapia with positive effects on the intestinal and liver histological features and the immune and antioxidative responses.

Exploring the Mechanisms and Therapeutic Approaches of Mitochondrial Dysfunction in Alzheimer’s Disease: An Educational Literature Review - Mostafa Hossam El Din Moawad; Ibrahim Serag; Ibraheem M. Alkhawaldeh; Abdallah Abbas; Abdulrahman Sharaf; Sumaya Alsalah; Mohammed Ahmed Sadeq; Mahmoud Mohamed Mohamed Shalaby; Mahmoud Tarek Hefnawy; Mohamed Abouzid; Mostafa Meshref (Molecular Neurobiology, 2025)
Alzheimer’s disease (AD) presents a significant challenge to global health. It is characterized by progressive cognitive deterioration and increased rates of morbidity and mortality among older adults. Among the various pathophysiologies of AD, mitochondrial dysfunction, encompassing conditions such as increased reactive oxygen production, dysregulated calcium homeostasis, and impaired mitochondrial dynamics, plays a pivotal role. This review comprehensively investigates the mechanisms of mitochondrial dysfunction in AD, focusing on aspects such as glucose metabolism impairment, mitochondrial bioenergetics, calcium signaling, protein tau and amyloid-beta-associated synapse dysfunction, mitophagy, aging, inflammation, mitochondrial DNA, mitochondria-localized microRNAs, genetics, hormones, and the electron transport chain and Krebs cycle. While lecanemab is the only FDA-approved medication to treat AD, we explore various therapeutic modalities for mitigating mitochondrial dysfunction in AD, including antioxidant drugs, antidiabetic agents, acetylcholinesterase inhibitors (FDA-approved to manage symptoms), nutritional supplements, natural products, phenylpropanoids, vaccines, exercise, and other potential treatments.

Novel Organic Formulations’ Utilization as Remediators for Salt-Affected Soil Improves Wheat Growth, Physio-Biochemical Attributes, Productivity, and Economic Profitability - Mostafa M. Rady; Hager K. H. Semida; Mahmoud A. Abdelfattah; Safia M. A. Ahmed; Ibrahim A. A. Mohamed; Clara R. Azzam (Journal of Soil Science and Plant Nutrition, 2025)
Overcoming the effects of soil salinity and maintaining agricultural productivity requires innovative technologies such as using novel organic formulations (NOFs) consisting of agricultural wastes, including compost of green bean plants (LCT) and maize silk (MS), with humic acid (HA). The effect of NOFs (HA + LCT, HA + MS, LCT + MS, and HA + LCT + MS) as soil remediators on the characteristics of saline soil (ECe = 7.03 dS m –1 ) and wheat plant performance grown in that soil was investigated. Compared with the control without any of the NOFs, all the NOFs applications considerably enhanced the soil organic matter (OM) content, nutrient contents, cation exchange capacity (CEC), and enzyme (urease, acid phosphatase, alkaline phosphatase, and catalase) activities with the superiority of HA + LCT + MS followed by LCT + MS treatment. The soil results were positively reflected in growth and physio-biochemical attributes of wheat plants. The best HA + LCT + MS treatment decreased leaf electrolyte leakage (39.5%) and hydrogen peroxide level (56.3%) while increasing chlorophyll content (59.0%), membrane stability index (30.8%), relative water content (34.3%), nutrient contents, K + /Na + ratio (67.0 and 59.0% for shoots and roots, respectively), antioxidant (glutathione, ascorbate, phenols, and flavonoids) levels, and antioxidant activity (24.0%) in wheat plants. All of the above positive results reflected an increase in plant growth traits such as shoot length (18.5%), leaf number plant –1 (10.1%), leaf area plant –1 (36.2%), shoot fresh weight (35.9%), and shoot dry weight (28.7%), and yield components like spike number plant –1 (56.8%), grain number spike –1 (28.7%), grain weight spike –1 (68.7%), and grain yield ha –1 (25.0%) with HA + LCT + MS treatment relative to the control. The beneficial impact of the HA + LCT + MS (followed by LCT + MS) formulation was more pronounced than other NOFs. Adding significant economic profitability, using the HA + LCT + MS (followed by LCT + MS) formulation to saline soil (ECe = 7.03 dS m –1 ) could mitigate the influences of soil salinity and improve wheat growth, physio-biochemical, and yield traits. Graphical Abstract Showing the effect of novel organic formulations on the physicochemical properties of salt-affected soil (ECe = 7.03 dS m −1 ) and the performance of wheat plants grown under the conditions of this salt-affected soil.

Mesoporous SiO2-chitin/MoO3 Nanocomposite: Synthesis, Surface Investigation, and Uptake Potential for Pb(II) and Cu(II) - Hany Fathy Heiba; Asia A. Taha; Alaa R. Mostafa; Abeer Elsaharty; Manal G. Mahmoud; Laila A. Mohamed (Environmental Processes, 2025)

Geochemistry of the U-bearing lithofacies within the major graben in Um Bogma area, Sinai, Egypt: implications for mineralization genesis and controlling factors - Ahmed E. Shata; Alaa Mostafa; Mahmoud M. Nasr; Ahmed M. Ismail; Hesham S. Serag El Din (Carbonates and Evaporites, 2025)

Optimizing dehydration and viscosity reduction in Egyptian heavy crude oil emulsions using eco-friendly demulsifiers - Ahmed Z. Ibrahim; El Sayed H. El tamany; Mostafa A.A. Mahmoud; Mokhtar Al-Abyadh; H.A. El Nagy (Fuel, 2025)

Physicochemical integration of egg white proteins and milk casein based on phase separation as a stable and optimized colloidal complex - Mohamed Salama; Mostafa Gouda; Mahmoud Abou-Elsoud; Xiaomeng Li; Xinyue Zhang; Long Sheng; Zhaoxia Cai (Food Hydrocolloids, 2025)

Numerical and field study of wick drains performance in soft clay - Mohamed Ashraf Kamal; Mohamed Hassanein Rabie; Hussein Mahmoud Hussein; Mohamed Abdelhamid Mostafa (Innovative Infrastructure Solutions, 2025)
The Soft soil formations are considered huge challenge for geotechnical engineers worldwide. Soft clay soil usually appears in coastal areas. This paper presents a field case study where the extended soft clay layers were a huge geotechnical challenge. The executed site investigation consists of boreholes and cone penetration tests (CPTu). The upper soft clay extends to depths more than 30m. Many field and laboratory tests were performed. The anticipated stresses due to the proposed structures were high for the existing soft soil deposits. The preloading system with vertical drains was selected as soil improvement system in some wide areas. Field instrumentation measurements were conducted in site during the preloading works. The detailed construction activities performed in the site are presented for two different areas. Both two-dimensional and three-dimensional finite element analyses are performed considering the construction activities for both areas. The results of the finite element analyses are compared with field measurement results. In addition, the final consolidation settlement due to the preloading load is estimated by different methods based on the recorded field measurements. The estimated results of final settlement are compared with the finite element analysis results. The presented results show that the use of preloading and vertical drains in the discussed project was successful and that the finite element analysis predictions were accurate.

Decorin alleviates non-alcoholic fatty liver disease in rats with polycystic ovary syndrome - Hany A. Elkattawy; Amira Ebrahim Alsemeh; Lashin Saad Ali; Mona Mostafa Ahmed; Asmaa Monir Eltaweel; Farha M. Shaikh; Ahmed Behiry; Ahmed El-Sayed Hassan; Deema Kamal Sabir; Dalia Mahmoud Abdelmonem Elsherbini; Sahar K. Ali; Madaniah Omar Zakari; et al. (Tissue and Cell, 2025)

Acetamiprid-induced pulmonary toxicity via oxidative stress, epithelial-mesenchymal transition, apoptosis, and extracellular matrix accumulation in human lung epithelial cells and fibroblasts: Protective role of heat-killed Lactobacilli - Samah S. Arafa; Heba A. Elnoury; Sahar Badr El-Din; Mohamed A. Sakr; Fatma Fawzi Hendawi; Rehab Ali Elsayed Masoud; Samia Soliman Barghash; Doaa Sabry Elbehairy; Ayat Abdelaty Hemeda; Islam Mostafa Farrag; Doaa Sayed Abdelrahman; Amira Mohammad Elsadek; et al. (Food and Chemical Toxicology, 2025)

Sandstorm Detection Using Attention Bi-LSTM UNet - Amira S. Mahmoud; Rasha M. El-Morshedy; Mohamed R. Metwalli; Marwa S. Mostafa (Journal of the Indian Society of Remote Sensing, 2025)

Prospective Hepatoprotective Actions of Novel Nano-formulations of Sildenafil and Neem Extract in Counteracting Oral Carbon Tetrachloride-induced Liver Injury in Rats - Mahmoud S. Sabra; Essmat A. H. Allam; Madeha H. A. Darwish; Al-Hassan Mohammed Mostafa; Abeer S. Hassan; Marwa G. Gamea; Dalia Hassan; Mohamed M. Elbadr (Journal of Pharmaceutical Innovation, 2025)
Purpose A multitude of inflammatory cells and chemical mediators initiate a complex cascade that ultimately leads to hepatocyte death and a systemic inflammatory response. This research aimed to investigate the potential effects of sildenafil and neem (Azadirachta indica) extract, in both conventional and nanoparticle (NP) forms, in the treatment of moderate acute liver damage induced by orogastric carbon tetrachloride (CCL 4 ). Methods To induce moderate acute hepatic damage a single oral dosage of CCL 4 (2.5 mL/kg body weight) was provided 24 h before euthanasia. In liver damage-induced CCL 4 , sildenafil and neem extract were given in conventional and nanoparticle (PLGA or niosome) forms. To find histological anomalies and hepatic changes, behavioral, biochemical, histopathological, and immunohistochemical methods were used. Results The findings indicated that sildenafil and/or neem extract, especially in NP combination, significantly mitigated CCL 4 -induced acute moderate liver damage. Indicators of liver function, including aspartate aminotransferase (AST), alkaline phosphatase (ALP), alanine aminotransferase (ALT), albumin, bilirubin and gamma-glutamyl transferase (GGT), shown improvement, particularly with the nanoparticulation of both therapies. Treatment, particularly in NP forms, improved the levels of malondialdehyde (MDA), superoxide dismutase (SOD), and glutathione peroxidase activity (GPx) in liver tissues. A significant reduction in NF-κB expression in hepatic tissue was shown in treatment groups. Also, medication resulted in lower levels of interleukin-1 beta (IL-1β), tumor necrosis factor alpha (TNF-α), caspase-3, and transforming growth factor-beta (TGF-β) in the liver tissue homogenates. Liver function was more significantly improved by the drug-NP combination. Conclusions This study verified the beneficial therapeutic effects of the combination of sildenafil and neem extract, particularly in NP forms, using biochemical, histological, and immunohistochemical analyses in a rat model of liver damage.

Isolation and in silico investigation of cannflavins from Cannabis sativa leaves as potential anti-SARS-CoV-2 agents targeting the Papain-Like Protease - Amira S. Wanas; Mohamed M. Radwan; Adel A. Marzouk; Eslam B. Elkaeed; Bshra A. Alsfouk; Ahmad E. Mostafa; Ibrahim H. Eissa; Ahmed M. Metwaly; Mahmoud A. ElSohly (Natural Product Research, 2025)

Omega-3 supplementation in migraine prophylaxis: An updated systematic review and meta-analysis - Haneen Sabet; Abdallah Abbas; Ibraheem M alkhawaldeh; Shrouk Ramadan; Moaz Elsayed Abouelmagd; Ebrahem Salah Abdul-Hamid; Ahmed Elbataa; Mona Mahmoud Elsakka; Anas Mansour; Mostafa Hossam El Din Moawad; Aynur Ozge (PharmaNutrition, 2025)

Performance and mechanism of a novel hydrolytic bacteria pretreatment to boost waste activated sludge disintegration and volatile fatty acids production during acidogenic fermentation - Eid S. Gaballah; Lei Gao; Emad A. Shalaby; Biao Yang; Mostafa Sobhi; Mahmoud M. Ali; Mohamed Samer; Chongpeng Tang; Guangcan Zhu (Journal of Environmental Management, 2025)

Pioneering study of Egyptian Neem and Jojoba extracts with molecular docking combat hospital multidrug resistant bacteria - Toka Khairy; Dina Hatem Amin; Hanaa Mohamed Salama; Iman Mohamed Amin Elkholy; Mostafa Elnakib; Hassan Mahmoud Gebreel; Hayam Abd Elnabi Sayed (Brazilian Journal of Microbiology, 2025)

Biosynthesis of trimetallic nanoparticles and their biological applications: a recent review - Amr H. Hashem; Ebrahim Saied; Bahaa M. Badr; Mohamed Soliman Dora; Mahmoud A. Diab; Amer Morsy Abdelaziz; Fathy M. Elkady; Mohamed Abdelrahman Ali; Nasser Ibrahim Issa; Ziad A. Hamdy; Mohamed E. Nafea; Ahmed Nageh Khalifa; et al. (Archives of Microbiology, 2025)

Preparation, characterization, and pesticide adsorption capacity of chitosan-magnetic graphene oxide nanoparticles with toxicological studies - Mohamed E. I. Badawy; Mostafa A. I. Taha; Reda K. Abdel-Razik; Mahmoud M. Abo-El-Saad (Environmental Science and Pollution Research, 2025)

Review: Chemical and biological features of genus Paralemnalia soft corals - Radwa Taher Mohie el-dien; Basma Khalaf Mahmoud; Amgad I. M. Khedr; Mohamed Salah Kamel; Mostafa A. Fouad (Medicinal Chemistry Research, 2025)

Feasibility of qualitative identification of some metal elements in rice grains using laser desorption ionization-time of flight mass spectrometry - Roya Mardanian; Hossein Farrokhpour; Mostafa Parandeh; Mahmoud Tabrizchi (Food Chemistry, 2025)

L-asparaginase-mediated pH shift and carbon dot fluorescence modulation: A sensitive ratiometric method for quantifying L-asparagine in diverse potato varieties under variable storage conditions - Khalid Alhazzani; Ahmed Z. Alanazi; Hossieny Ibrahim; Aya M. Mostafa; James Barker; Ashraf M. Mahmoud; Mohamed M. El-Wekil; Al-Montaser Bellah H. Ali (Food Chemistry, 2025)

A novel pharmacological strategy using nanoparticles with glutathione and virgin coconut oil to treat gentamicin-induced acute renal failure in rats - Mahmoud S. Sabra; Essmat A. H. Allam; Mohamed Abd El-Aal; Nessma H. Hassan; Al-Hassan Mohammed Mostafa; Ahmed A. N. Ahmed (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)
In acute renal failure (ARF), the glomerular filtration rate is reduced, and nitrogenous waste products accumulate persistently, which can last anywhere from a few hours to several days. There is hope for a reversal of the rapid loss of renal function caused by this condition. This study, with gentamicin-induced acute ARF as a prospective setting, sets out to examine the reno-protective benefits of virgin coconut oil (VCO) and GSH. Furthermore, the study evaluated the effect of medication nanoparticle compositions on several kidney function markers. The induction of ARF is achieved with the intraperitoneal injection of gentamicin. To assess renal function, rats underwent 24 h of dehydration and hunger before their deaths. The study examined various aspects, including kidney function tests, markers of oxidative stress, histology of kidney tissue, inflammatory cytokines, immunohistochemistry expression of nuclear factor-kappa B (NF-κB), and specific biomarkers for kidney tissue damage, such as kidney injury molecule-1 (KIM-1) and neutrophil gelatinase–associated lipocalin (NGAL). The results of our study indicated that the combination of VCO and GSH, using both regular and nanoparticle formulations, had a better protective impact on the kidneys compared to using either drug alone. The recovery of renal tissue and serum markers, which are symptomatic of organ damage, indicates improvement. This was also demonstrated by the reduction in tubular expression of TNF-α, IL-1β, KIM-1, and NGAL. The immunohistochemical studies showed that the combination therapy, especially with the nanoforms, greatly improved the damaged cellular changes in the kidneys, as shown by higher levels of NF-κB. The study shows that VCO and GSH, when administered individually or combined, significantly improve ARF in a gentamicin-induced rat model, highlighting potential therapeutic implications. Notably, the combined nanoparticulate formulations exhibit substantial effectiveness.

New sesquiterpenes from the soft coral Litophyton arboreum - Amany Hamouda Mahmoud; Sabry A. H. Zidan; Mamdouh Nabil Samy; Abdallah Alian; Mahmoud A. A. Ibrahim; Mostafa Ahmed Fouad; Mohamed Salah Kamel; Katsuyoshi Matsunami (Journal of Natural Medicines, 2025)
Two new sesquiterpenes; 8α,11-dihydroxy-β-cyperon ( 2 ), and 5- epi -7α-hydroxy-( +)-oplopanone ( 3 ), were isolated from the soft coral Litophyton arboreum, together with nine known ones, including five sesquiterpenes; 11-hydroxy-8-oxo-β-cyperon ( 1 ), alismoxide ( 4 ), 5β,8β-epidioxy-11-hydroxy-6-eudesmene ( 5 ), chabrolidione B ( 6 ), 7-oxo-tri-nor-eudesm-5-en-4β-ol ( 7 ), two sterols; 7β-acetoxy-24-methyl-cholesta-5,24(28)-diene-3β,19-diol ( 8 ), nebrosteroid M ( 9 ), and two glycerol derivatives; chimyl alcohol ( 10 ) and batyl alcohol ( 11 ). The structures of the isolated compounds were characterized using spectroscopic techniques, predominately HR-ESI–MS, 1D, 2D-NMR, and ECD analyses. Compounds 1 – 11 were evaluated for their cytotoxic activity against three human cancer-cell lines (A549, MCF-7 and HepG2), and anti-leishmanial potential against the causal parasite, Leishmania major. Compounds 4 , 8 , and 9 exhibited potent cytotoxic activity against the A549 cell line (IC 50 = 17.0 ± 2.5, 13.5 ± 2.1, and 16.5 ± 1.3 μg/ml, respectively) as compared with the standard antitumor agent etoposide (IC 50 28.4 ± 4.5 μg/ml). In addition, compound 9 exhibited remarkable cytotoxic activity against MCF-7 cell line (IC 50 = 24.7 ± 2.1 μg/ml: 22.2 ± 4.2 μg/mL for etoposide). Graphical abstract

Impact of restraining position on tonic immobility in broiler chickens and mule ducks - Usama T. Mahmoud; Frank A.M. Tuyttens; Mostafa Farghal; Ghada Abd El-Reda; Ramadan D. EL Shoukary (Applied Animal Behaviour Science, 2025)

Protective effect of epidermal growth factor on cryopreservation of dromedary camel epididymal spermatozoa: Evidence from in vitro and in silico studies - Sameh A. Abdelnour; Wael A. Khalil; Mahmoud A.E. Hassan; Ibrahim T. El-Ratel; Mostafa A. El-Harairy; Sherif M. Dessouki; Kandil A.A. Attia (Animal Reproduction Science, 2025)

Characterization, surface deformation analysis and sources of small plastic fragments collected in diverse environments of Egypt - Mohamed Hamed; Wafa Mazi; Ibrahim Saleem Alatawi; Noha Omer; Rasha Jame; Mahmoud A. Abdelaziz; Mostafa A. Khaled (Marine Pollution Bulletin, 2024)

Attenuation of inflammation, oxidative stress and TGF-β1/Smad3 signaling and upregulation of Nrf2/HO-1 signaling mediate the protective effect of diallyl disulfide against cadmium nephrotoxicity - Reem S. Alruhaimi; Emad H.M. Hassanein; Ahmad F. Ahmeda; Sulaiman M. Alnasser; Ahmed M. Atwa; Mostafa Sabry; Mohammed A. Alzoghaibi; Ayman M. Mahmoud (Tissue and Cell, 2024)

Diallyl disulfide prevents cadmium-induced testicular injury by attenuating oxidative stress, apoptosis, and TLR-4/NF-κB and JAK1/STAT3 signaling and upregulating SIRT1 in rats - Emad H.M. Hassanein; Mohammed F. Alotaibi; Reem S. Alruhaimi; Omnia A.M. Abd El-Ghafar; Mostafa K. Mohammad; Ahmed M. Atwa; Ayman M. Mahmoud (Journal of Trace Elements in Medicine and Biology, 2024)

Valorization of abattoir water discharge through phycoremediation for enhanced biomass and biodiesel production - Mahdy Elsayed; Yevheniia Mysnyk; Mohamed Mahmoud-Aly; Ehab Mostafa; Adel W. Almutairi; Doaa G. Abbas; Mohamed M. Ibrahim; Dieter Hanelt; Abdelfatah Abomohra (Biomass and Bioenergy, 2024)

Soil–plant Integrative Supplementation with Humic Acid and Antioxidants Improves Growth, Fruit Quality, and Antioxidant Capacity of Cd-stressed Solanum Melongena - Ali A. S. Sayed; Zahra Seoudi; Ashraf Sh. Osman; Wael M. Semida; Mostafa M. Rady; Amr Elkelish; Amr E. M. Mahmoud (Journal of Soil Science and Plant Nutrition, 2024)

Hydrocarbon-Source Correlation in the Obayied Sub-Basin, North Western Desert, Egypt: Controls on Generation of Natural Gas and Light Crude Hydrocarbon Blends - Mostafa Hassan; Mahmoud Lotfy Leila; Mohammed Ahmed; Ghalib Issa; Branimir Šegvić; Omar Hegab (Journal of Earth Science, 2024)

Areal-source and fault-source based probabilistic seismic hazard analysis using characteristic earthquake model and Monte-Carlo approach: An example of the Gulf of Aqaba region - Vladimir Sokolov; Hani Mahmoud Zahran; Mostafa Toni (Soil Dynamics and Earthquake Engineering, 2024)

Analyzing the impacts of climate change on ecosystem services provided by apple orchards in Southeast France using a process-based model - Gilles Vercambre; José M. Mirás-Avalos; Perrine Juillion; Mostafa Moradzadeh; Daniel Plenet; Pierre Valsesia; Mohamed-Mahmoud Memah; Marie Launay; Vincent Lesniak; Bruno Cheviron; Michel Genard; Francoise Lescourret (Journal of Environmental Management, 2024)

Efficient degradation of benzalkonium chloride (BAC) by zero-valent iron activated persulfate: Kinetics, reaction mechanisms, theoretical calculations and toxicity evolution - Yumeng Qi; Wenqian Cao; Ying Zhang; Ruijuan Qu; Rehab Khaled Mahmoud; Mostafa R. Abukhadra; Zongli Huo; Feng Zhu (Environmental Pollution, 2024)

Linagliptin mitigates cisplatin-induced kidney impairment via mitophagy regulation in rats, with emphasis on SIRT-3/PGC-1α, PINK-1 and Parkin-2 - Mohamed Gamal El-Din Ewees; Gomaa Mostafa-Hadeab; Sameh Saber; Eman Ali Abd El-Meguid; Haidy Tamer Abo Sree; Fatema El-Zahraa S. Abdel Rahman; Nesreen Ishak Mahmoud (Toxicology and Applied Pharmacology, 2024)

Towards the preparation of sustainable superplasticizers for geopolymeric pastes via radiation-induced grafting of sulfonic group-bearing monomers onto corn starch - Noha M. Deghiedy; Safaa M.A. El-Gamal; Mohamed Ramadan; Alaa Mohsen; Mahmoud M. Hazem; Mostafa A. Sayed; Fatma M. Helmy; Mona M. Wetwet; Ahmed E. Swilem (Carbohydrate Polymers, 2024)

Automatic Building Extraction from Multispectral LiDAR Using Novel 3D Spatial Indices and Deep Learning Point CNN - Asmaa A. Mandouh; Mahmoud El Nokrashy O. Ali; Mostafa H. A. Mohamed; Lamyaa Gamal E. L.-Deen Taha; Sayed A. Mohamed (Journal of the Indian Society of Remote Sensing, 2024)

Efficacy of cannabis-based medicine in the treatment of Tourette syndrome: a systematic review and meta-analysis - Ibrahim Serag; Mona Mahmoud Elsakka; Mostafa Hossam El din Moawad; Hossam Tharwat Ali; Khalid Sarhan; Sally Shayeb; Islam Nadim; Mohamed Abouzid (European Journal of Clinical Pharmacology, 2024)
Background Tourette syndrome (TS) is a neurodevelopmental disorder characterized by motor and phonic tics. It is a condition that affects between 0.3% and 0.7% of children, and its pathophysiology remains largely elusive. TS is associated with structural and functional alterations in corticostriatal circuits and neurochemical imbalances. Even though TS is currently incurable, there are established treatment options available, including behavioral therapy and neuroleptics. The use of cannabis-based medicine for tic management is an emerging therapeutic strategy, although its efficacy is still under investigation. It is hypothesized to interact with the endogenous cannabinoid system, but further research is required to ascertain its safety and effectiveness in TS. Aim In our systematic review and meta-analysis, we aim to assess the effectiveness of cannabis-based medicine in the treatment of TS. Methods We searched PubMed, Cochrane, Scopus, and Web of Sciences until February 2024. We included clinical trials and cohort studies investigating the efficacy of cannabis-based medicine in the treatment of TS. Data extraction focused on baseline characteristics of the included studies and efficacy outcomes, including scores on the Yale Global Tic Severity Scale (YGTSS), Premonitory Urge for Tics Scale (PUTS), and Yale-Brown Obsessive Compulsive Scale (Y-BOCS). We conducted the meta-analysis using Review Manager version 5.4. software. We compared the measurements before and after drug intake using mean difference (MD) and 95% confidence interval (CI). Results In total, 357 articles were identified for screening, with nine studies included in the systematic review and 3 in the meta-analysis. These studies involved 401 adult patients with TS treated with cannabis. YGTSS revealed a significant reduction in total scores (MD = -23.71, 95% CI [-43.86 to -3.55], P = 0.02), PUTS revealed a significant decrease in scores (MD = -5.36, 95% CI [-8.46 to -2.27], P = 0.0007), and Y-BOCS revealed no significant difference in score reduction (MD = -6.22, 95% CI [-12.68 to 0.23], P = 0.06). Conclusion The current study indicates promising and potentially effective outcomes with the use of cannabis-based medicine in mitigating the severity of tics and premonitory urges. However, there is a need for larger, placebo-controlled studies with more representative samples to validate these findings.

Correction: Comprehensive approach integrating water quality index and toxic element analysis for environmental and health risk assessment enhanced by simulation techniques - Mohamed Hamdy Eid; Mahmoud Awad; Essam A. Mohamed; Tamer Nassar; Mostafa R. Abukhadra; Ahmed M. El-Sherbeeny; Attila Kovács; Péter Szűcs (Environmental Geochemistry and Health, 2024)

Comprehensive approach integrating water quality index and toxic element analysis for environmental and health risk assessment enhanced by simulation techniques - Mohamed Hamdy Eid; Mahmoud Awad; Essam A. Mohamed; Tamer Nassar; Mostafa R. Abukhadra; Ahmed M. El-Sherbeeny; Attila Kovács; Péter Szűcs (Environmental Geochemistry and Health, 2024)
Due to water shortages and the potential impact of Ethiopia’s new dam on the Nile River, Egypt is seeking new water resources. This study assesses the drinking water quality and associated risks from potentially toxic elements (PTEs) in the Quaternary aquifer (QA) in Beni-Suef, Egypt. Using a comprehensive approach, including PHREEQC geochemical modeling, ionic ratios, multivariate statistical analyses, and the integrated weight water quality index (WQI), the study evaluated the sources of ion contamination and the mixing of Nile water with QA. Various indices, such as the Heavy Metal Pollution Index (HPI), ecological Risk Index (RI), Hazard Quotient (HQ), and Hazard Index (HI), were used to assess ecological and health risks. Monte Carlo simulations provided probabilistic assessments of non-carcinogenic risks for adults and children. GIS tools were used to map risk indices, identifying the most deteriorated locations for sustainable management. The hydrochemical analysis revealed water facies including Na–Cl, Ca–Mg–HCO 3 , and mixed types, influenced by carbonate dissolution, ion exchange, and silicate weathering. Contamination sources, particularly in the north and south, were linked to agricultural activities, irrigation return flow, municipal waste, and evaporation. The WQI indicated that 10.14% of samples were extremely poor, 21.7% were poor, 26% were medium, and 42% were good to excellent. PTE contamination varied, with HPI values indicating good water quality in the central area in 53.6% of the collected samples (HPI < 30), but contamination in the north and south is high (HPI > 51). Ecological Risk Index values were below the threshold in 100% of samples (RI < 30), confirming water safety regarding PTEs. In comparison, for hazard index (HI) through oral/ingestion, adults exhibited HI values ranging from 0.012 to 2.16, while children showed higher values, ranging from 0.045 to 8.25. However, the hazard index for oral/ingestion exceeded safe limits in the north and south (HI oral > 1), posing non-carcinogenic risks. Monte Carlo simulations revealed significant risks from oral exposure to manganese (HQ oral > 1), particularly in El-Wasta and El-Fashn, necessitating further treatment and management.

The Effect of Metallic Nanoparticles Supplementation in Semen Extender on Post-thaw Quality and Fertilizing Ability of Egyptian Buffalo (Bubalus bubalis) Spermatozoa - Wael A. Khalil; Mohamed S. El-Rais; Mohamed M. Hegazy; Mahmoud A. E. Hassan; Ali A. El-Raghi; Mostafa M. El-Moghazy (Biological Trace Element Research, 2024)
Nanomaterials offer several promising prospects in the field of farm animal reproduction, encompassing a broad range of applications such as transgenesis and the precise delivery of substances to sperm cells, antimicrobial, antioxidants properties as well as their potent role in improving cryopreservation methods. The aim of the present study is to explore the effect of supplementing the semen extender with 10 µg/mL nano gold (Au-NPs10), 10 µg/mL nano silver (Ag-NPs10), 1 µg/mL nano selenium (Se-NPs1), and 100 µg/mL nano zinc oxide (ZnO-NPs100) on sperm characteristics and kinematics parameters, acrosome integrity, oxidative biomarkers, morphological and apoptosis-like changes of frozen-thawed buffalo bull sperm, and, ultimately, their fertilizing capacity. The results revealed that all aforementioned nano materials significantly improved viability, progressive motility, membrane integrity, acrosome integrity, and kinematic parameters as well as apoptosis-like changes of post-thawed buffalo bull sperm compared to the control ( p < 0.05). No discernible effects were observed on sperm ultrastructure morphology measures as a response to the addition of these metallic nanoparticles to the extender. The values of caspase 3 significantly decreased by 64.22, 45.99, 75.59, and 49.39% in Au-NPs10, Ag-NPs10, Se-NPs1, and ZnO-NPs100 treated groups, respectively, compared to the control. The addition of 100 µg ZnO-NPs to the extender significantly decreased the total count of bacteria, fungi, and yeast compared to the control ( p < 0.05). The AuNPs10 and SeNPs1 treated groups showed lower content of malondialdehyde, hydrogen peroxide, and nitric oxide concentrations and higher values of total antioxidant capacity of post-thawed extended semen ( p < 0.05). Pregnancy rates increased by 17.5, 20, and 30% in buffalo cows inseminated with sperm treated with ZnO-NPs100, Se-NPs1, and Au-NPs10, respectively, compared to the control group. The present results indicate that the freezing extender supplemented with metallic nanoparticles can be an effective strategy to enhance the cryotolerance and fertility potential of buffalo bull sperm.

Experimental insights and modeling innovations: Deciphering Fe(VI) oxidation in imidazole ionic liquids through QSAR and RFR - Beibei Li; Ruijuan Qu; Ting Wang; Ruixue Guo; Jie Tian; Shuyi Li; Mostafa R. Abukhadra; Rehab Khaled Mahmoud; Zunyao Wang (Journal of Hazardous Materials, 2024)

Synergistic Effects of Microbial Gibberellic Acid and Vitamins on Onion (Allium cepa L.) Yield, and Quality in Low-Fertility Soil - Ghada Abd-Elmonsef Mahmoud; Mohamed Hefzy; Mostafa M. A. A. Zahran (Journal of Soil Science and Plant Nutrition, 2024)
Onion is one of the most popular vegetables that play a major role in boosting immunity against diseases. As a result of the successive population increase, many farmers resort to excessive use of chemical plant growth enhancers to increase the crop's productivity, which causes many health and environmental problems and reduces the sustainability of the soil. Microbial phytohormones and vitamins are safe, eco-friendly, and effective natural solutions to increase the crop's productivity and maintain the soil health at the same time. To our knowledge, until know there is no information about the roles of microbial gibberellic acid (GA 3 ), and vitamins on the growth and quality traits of onions. Two field experiments were conducted during two consecutive winter seasons in a sandy calcareous soil farm. Two treatments were in the main plot (without and with microbial GA 3 ), and six were in the sub-plot (control, chemical thiamine, ascorbic acid, riboflavin, and microbial ascorbic acid and riboflavin). Plant growth parameters including plant height, fresh weight, leaf number, bulb diameter, and neck diameter were recorded. Onion yield and their quality traits of sugar content, protein, antioxidants, vitamin C, phenols, flavonoids, and NPK were measured. The major findings revealed that plants treated with applications of microbial GA 3 or vitamin treatments significantly improved the onion yield, phenotypic, physiological, and biochemical characteristics in both seasons. In the majority of the measured parameters, the microbial ascorbic acid treatment outperformed the other vitamin treatments. The combination of foliar microbial GA 3 spray and vitamins, especially microbial ascorbic acid, and microbial riboflavin, produced the high onion yield, growth and quality traits of plant height, number of leaves, fresh weights, bulb diameter, sugar content, vitamin C, total antioxidants, total phenols, and flavonoids during both seasons. The application of microbial GA 3 in combination with microbial vitamins as foliar spraying are promising eco-friendly, cheap, plant bio-stimulators that could be used safely in the field, especially under low-fertility soil, for good growth, yield, and high-quality onions.

The Role of Chlorella vulgaris in Attenuating Infertility Induced by Cadmium Chloride via Suppressing Oxidative Stress and Modulating Spermatogenesis and Steroidogenesis in Male Rats - Mayada R Farag; Nesma I. El-naseery; Eman I. El behery; Doaa S. Nouh; Amany El-Mleeh; Ismail M.A. Mostafa; Mahmoud Alagawany; Alessandro Di Cerbo; Mahmoud M. Azzam; Suzan A. Mawed (Biological Trace Element Research, 2024)

Sustainable and Green Fluorescence Method for the Determination of Cloperastine in Human Plasma: Greenness Assessment - Abobakr A. Mohamed; Mahmoud A. Omar; Eman Alzahrani; Mohamed A. Abdel-Lateef; Islam M. Mostafa (Journal of Fluorescence, 2024)

Influence of Dietary Probiotic and Alpha-Monolaurin on Performance, Egg Quality, Blood Constituents, and Egg Fatty Acids’ Profile in Laying Hens - Ahmed A. Saleh; Livio Galosi; Mahmoud Metwally; Mohammed Ragab; Mahmoud Hamza; Mostafa Shukry; Medhat Khairy; Mohammed H. Alzawqari; Mahmoud M. Azzam; Mahmoud Alagawany (Probiotics and Antimicrobial Proteins, 2024)

Chemical control of wheat sunn pest, Eurygaster integriceps, by UAV sprayer and very low volume knapsack sprayer - Aziz Sheikhigarjan; Mahmoud Safari; Mostafa Mansour Ghazi; Ali Zarnegar; Shahram Shahrokhi; Nikrooz Bagheri; Saeed Moein; Peyman Seyedin (Phytoparasitica, 2024)

Mesoporous magnetic biochar derived from common reed (Phragmites australis) for rapid and efficient removal of methylene blue from aqueous media - Wael Ibrahim Mortada; Mahmoud Mohsen Ghaith; Nada Elsayed Khedr; Mostafa Ibrahim Ellethy; Alaa Waleed Mohsen; Amira Labib Shafik (Environmental Science and Pollution Research, 2024)
A novel mesoporous magnetic biochar (MBC) was prepared, using a randomly growing plant, i.e., common reed, as an exporter of carbon, and applied for removal of methylene blue (MB) from aqueous solutions. The prepared sorbent was characterized by nitrogen adsorption/desorption isotherm, saturation magnetization, pH of point of zero charges (pH PZC ), Fourier-transform infrared spectroscopy (FT-IR), and scanning electron microscopy (SEM). The obtained MBC has a specific surface area of 94.2 m 2 g −1 and a pore radius of 4.1 nm, a pore volume of 0.252 cm 3 g −1 , a saturation magnetization of 0.786 emu g −1 , and a pH PZC of 6.2. Batch adsorption experiments were used to study the impact of the physicochemical factors involved in the adsorption process. The findings revealed that MB removal by MBC was achieved optimally at pH 8.0, sorbent dosage of 1.0 g L −1 , and contact time of 30 min. At these conditions, the maximum adsorption was 353.4 mg g −1 . Furthermore, the adsorption isotherm indicated that the Langmuir pattern matched well with the experimental data, compared to the Freindlich model. The ∆ G was − 6.7, − 7.1, and − 7.5 kJ mol −1 , at 298, 308, and 318 K, respectively, indicating a spontaneous process. The values of ∆ H and ∆ S were 5.71 kJ mol −1 and 41.6 J mol −1 K −1 , respectively, suggesting endothermic and the interaction between MB and MBC is van der Waals type. The absorbent was regenerated and reused for four cycles after elution with 0.1 mol L −1 of HCl. This study concluded that the magnetic biochar generated from common reed has tremendous promise in the practical use of removing MB from wastewater. Graphic Abstract

The Role of RIN3 Gene in Alzheimer’s Disease Pathogenesis: a Comprehensive Review - Mostafa Meshref; Hazem S. Ghaith; Mohamed Ahmed Hammad; Mahmoud Mohamed Mohamed Shalaby; Faris Ayasra; Fatma Ahmed Monib; Mohamed S. Attia; Mahmoud A. Ebada; Hanaa Elsayed; Ali Shalash; Eshak I. Bahbah (Molecular Neurobiology, 2024)
Alzheimer’s disease (AD) is a globally prevalent form of dementia that impacts diverse populations and is characterized by progressive neurodegeneration and impairments in executive memory. Although the exact mechanisms underlying AD pathogenesis remain unclear, it is commonly accepted that the aggregation of misfolded proteins, such as amyloid plaques and neurofibrillary tau tangles, plays a critical role. Additionally, AD is a multifactorial condition influenced by various genetic factors and can manifest as either early-onset AD (EOAD) or late-onset AD (LOAD), each associated with specific gene variants. One gene of particular interest in both EOAD and LOAD is RIN3, a guanine nucleotide exchange factor. This gene plays a multifaceted role in AD pathogenesis. Firstly, upregulation of RIN3 can result in endosomal enlargement and dysfunction, thereby facilitating the accumulation of beta-amyloid (Aβ) peptides in the brain. Secondly, RIN3 has been shown to impact the PICLAM pathway, affecting transcytosis across the blood-brain barrier. Lastly, RIN3 has implications for immune-mediated responses, notably through its influence on the PTK2B gene. This review aims to provide a concise overview of AD and delve into the role of the RIN3 gene in its pathogenesis.

Differential Physiological and Molecular Processes in the Root May Underlie Contrasting Salt Tolerance in Two Egyptian Rice Cultivars at the Seedling Stage - Ahmad Mohammad M. Mekawy; Dekoum V.M. Assaha; Jiacheng Li; Asmaa Yusuf; Doaa Mostafa; Mahmoud Ali Shoulkamy; Akihiro Ueda (Journal of Soil Science and Plant Nutrition, 2024)
This study aimed to compare various responses of two Egyptian rice accessions bred for high yields, Sakha108 and Giza177, to salt stress at the seedling stage. Twenty-eight-day-old seedlings of two cultivars were grown in a hydroponic medium under control conditions (no NaCl) and salt stress (75 mM NaCl) for 12 days. Growth (dry weight), Na + and K + concentrations, enzymatic and non-enzymatic antioxidants, malondialdehyde (MDA), hydrogen peroxide (H 2 O 2 ), and expression of Na + and K + transport-coding genes were recorded. Sakha108’s growth (18% rise from control) was significantly higher than Giza177’s. Both cultivars accumulated similar amounts of Na + in the leaves and sheaths, however, Sakha108 had higher Na + concentrations in the roots than Giza177 (13.3% higher). Root K + concentration dropped dramatically (~ 2-fold reduction) in Giza177 roots while remaining unchanged in Sakha108 roots. The concentrations of H 2 O 2 (root) and MDA (leaf and root) were higher in Giza177 than in Sakha108, although the difference was not statistically significant. Proline and total flavonoid (TF) contents in Sakha108 roots were greater than those in Giza177 roots. The expression of OsHKT1;5 and OsHKT2;1 genes declined in both cultivars, whereas expressions of OsSOS1 , OsNHX1 , and OsHAK7 were induced in Sakha108 but, except for OsHAK7 , were repressed in Giza177. Combined, these findings suggest that Sakha108 is more resistant to salt stress than Giza177 is, and that this variation in tolerance may have its origins in the root systems of the two cultivars. Thus, these adaptive traits in the root of Sakha 108 could be explored for engineering stress tolerance in susceptible but high-yielding rice cultivars.

Assessment of the Effect of Surface Modification of Metal Oxides on Silver Nanoparticles: Optical Properties and Potential Toxicity - Ahmed Soltan Monem; Heba Mohamed Fahmy; Ayaat Mahmoud Mosleh; Eman Mohamed Salama; Mostafa Mohamed Ahmed; Esraa Ahmed Abu El Qassem Mahmoud; Bsma Hassan Nour; Mohamed Mahmoud Fathy (Cell Biochemistry and Biophysics, 2024)

Fine-tuning Fluorescence of Amlodipine Adopting on Blocking of Photoinduced Electron Transfer (PET): Application in Human Plasma - Ahmed M. Shehata; Mahmoud A. Omar; Islam M. Mostafa; Hossein M. Elbadawy; Mohammed Almaghrabi; Abobakr A. Mohamed (Journal of Fluorescence, 2024)

Dissipation behavior, residue distribution, and exposure risk assessment of tebufenpyrad and milbemectin acaricides in strawberries under open field conditions - Farag Malhat; Mostafa Mahmoud; Dalia A. Barakat; El-Desoky Ibrahim; Hassan Elgammal; Mohamed Hussien; Ayman N. Saber (Environmental Science and Pollution Research, 2024)

The beneficial effects of quinoa seed extract supplementation on ram sperm quality following cryopreservation - Wael A. Khalil; Mahmoud A.E. Hassan; Sally Ibrahim; Amer K. Mohammed; Mostafa A. El-Harairy; Sameh A. Abdelnour (Animal Reproduction Science, 2024)

Event-based rainfall analysis in Sinai, Egypt - Tamer A. Gado; Mohamed Elkollaly; Yiping Guo; Rufayda M. El-Hagrsy; Mahmoud B. Mohameden; Basma A. Shalaby; Bahaa Elboshy; Hewida Omara; Mostafa A. ElSawwaf (Hydrological Sciences Journal, 2024)

Modulation of the Sirtuin-1 signaling pathway in doxorubicin-induced nephrotoxicity (synergistic amelioration by resveratrol and pirfenidone) - Samia Mahmoud Manawy; Eman Mohamed Faruk; Rabab Fawzy Hindawy; Mahmoud M. Hassan; Diaa M.G. Farrag; Mansour A.E. Bashar; Hanan Fouad; Rania Abubaker Bagabir; Dina Allam Abdelmaksoud Hassan; Ahmed Mohammed Zaazaa; Mohamed Ghazy Attia Hablas; K Mostafa Kamal (Tissue and Cell, 2024)

Effect of titanium oxide/reduced graphene (TiO2/rGO) addition onto water flux and reverse salt diffusion thin-film nanocomposite forward osmosis membranes - Amira M. Shawky; Yousra H. Kotp; Mahmoud A. Mousa; Mostafa M. S. Aboelfadl; Eisa E. Hekal; Khaled Zakaria (Environmental Science and Pollution Research, 2024)
Thin-film nanocomposite (TFN) forward osmosis (FO) membranes have attracted significant attention due to their potential for solving global water scarcity problems. In this study, we investigate the impact of titanium oxide (TiO 2 ) and titanium oxide/reduced graphene (TiO 2 /rGO) additions on the performance of TFN-FO membranes, specifically focusing on water flux and reverse salt diffusion. Membranes with varying concentrations of TiO 2 and TiO 2 /rGO were fabricated as interfacial polymerizing M-phenylenediamine (MPD) and benzenetricarbonyl tricholoride (TMC) monomers with TiO 2 and its reduced graphene composites (TiO 2 /rGO). The TMC solution was supplemented with TiO 2 and its reduced graphene composites (TiO 2 /rGO) to enhance FO performance and reverse solute flux. All MPD/TMC polyamide membranes are characterized using various techniques such as scanning electron microscopy (SEM), atomic force microscopy (AFM), and contact angle measurements. The results demonstrate that incorporating TiO 2 /rGO into the membrane thin layer improves water flux and reduces reverse salt diffusion. In contrast to the TFC membrane (10.24 L m −2 h −1 and 6.53 g/m 2 h), higher water flux and higher reverse solute flux were detected in the case of TiO 2 and TiO 2 /rGO-merged TFC skin membranes (18.81 and 24.52 L m −2 h −1 and 2.74 and 2.15 g/m 2 h, respectively). The effects of TiO 2 and TiO 2 /rGO stacking on the skin membrane and the performance of TiO 2 and TiO 2 /rGO skin membranes have been thoroughly studied. Additionally, being investigated is the impact of draw solution concentration. Graphical Abstract

Ultrasensitive Visual Tracking of Toxic Cyanide Ions in Biological Samples Using Biocompatible Metal–Organic Frameworks Architectures - Islam M. El-Sewify; Mohamed A. Shenashen; Rasha F. El-Agamy; Mohammed S. Selim; Norah F. Alqahtani; Ahmed Elmarakbi; Mitsuhiro Ebara; Mahmoud M. Selim; Mostafa M.H. Khalil; Sherif A. El-Safty (Journal of Hazardous Materials, 2024)

Parasitological, Serological and Molecular Prevalence of Trypanosoma evansi among Arabian Camels (Camelus dromedaries) with Evaluation of Antitrypanosomal Drugs - Ahmed Abdel-Rady; Abdullah Alhassan; Walaa Mostafa; Mahmoud M. Elhaig (Acta Parasitologica, 2024)

Polyethyleneimine-assisted growth of NiCo2S4/Co2C on carbon matrix towards a high-performance supercapacitor electrode - Reham Ehab Mostafa; S.S. Mahmoud; N.S. Tantawy; Saad G. Mohamed (Chemical Engineering Journal, 2024)

The effect of irrigation management on rice grain yield, irrigation water productivity and methane emissions in northern Iran - Mostafa Yousefian; Ali Shahnazari; Mirkhalegh Z. Ahmadi; Mahmoud Raeini Sarjaz; Behrouz Arabzadeh (Irrigation and Drainage, 2024)
This experiment aims to study the effect of water‐saving irrigation on rice production and methane emissions. Three irrigation methods, that is, flooding irrigation, deficit irrigation (DI) and alternate partial root‐zone drying (APRD), were employed in a 2‐year field trial. The experiment was conducted in a randomized complete block design with three replications. For the DI and APRD treatments, plots were not irrigated until the soil matric potential reached −10 (DI10 and APRD10), −30 (DI30 and APRD30) and −60 kPa (DI60 and APRD60). In the APRD treatments, two adjacent furrows of each plant row were alternately irrigated in consecutive irrigation events. The DI and APRD treatments did not affect yield components when the soil matric potential was −10 kPa. Applying APRD treatments increased irrigation water productivity by 45%, 51% and 31% for soil matric potentials of −10, −30 and −60 kPa, respectively. On average, water stress treatments reduced methane emissions by 78% compared to flooding treatment. On average, the APRD treatments decreased the water input by 10% compared with the DI treatments while achieving a 2.5% higher yield. This is the first study to outline the effect of APRD on methane emissions and rice production. These findings suggest that APRD could be a valuable strategy to mitigate methane emissions without risking rice yield reduction.

Aureanin: a new iridoid from the leaves of Tabebuia aurea (Silva Manso) Benth. & Hook.f. ex S.Moore - Amany Hamouda Mahmoud; Basma Khalaf Mahmoud; Mamdouh Nabil Samy; Mostafa Ahmad Fouad; Mohamed Salah Kamel; Katsuyoshi Matsunami (Natural Product Research, 2024)

Performance evaluation of multifunctional windows for commercial buildings under hot-humid climatic environments - Mostafa M. Abd El-Samie; O.E. Mahmoud; Yue Yang; M Fatouh (Energy and Buildings, 2024)

Effect of olive, flaxseed, and grape seed nano-emulsion essential oils on semen buffalo freezability - Wael A. Khalil; Mahmoud A.E. Hassan; Kandil A.A. Attia; Hassan A. El-Metwaly; Mostafa A. El-Harairy; Abdelaziz M. Sakr; Sameh A. Abdelnour (Theriogenology, 2023)

Rhein methotrexate-decorated solid lipid nanoparticles altering adjuvant arthritis progression through endoplasmic reticulum stress-mediated apoptosis - Wessam M. El-Refaie; Mostafa S. Ghazy; Fady A. Ateyya; Eman Sheta; Mohanad Y. Shafek; Mahmoud S. Ibrahim; Mahmoud MA. Ismail; Mennatallah A. Gowayed (Inflammopharmacology, 2023)
Methotrexate (MTX) and diacerein (DIA) are two of the most potent disease-modifying anti-rheumatic drugs used for the treatment of rheumatoid arthritis (RA). DIA has reflected some GIT and hepatobiliary manifestations in numerous cases. It undergoes biotransformation in the liver into the active metabolite rhein (RH) which is characterized by its excellent anti-inflammatory activity and lower side effects. However, RH's hydrophobic nature and low bioavailability do not encourage its use in RA. The current study aims to use RH in combination with MTX in targeted solid lipid nanoparticles (RH-MTX-SLNs) for better effectiveness and shadowing light on its possible mechanistic pathways. RH-MTX-SLNs were prepared and assessed for their quality attributes. The effect of the formulation was assessed in-vivo in an adjuvant arthritis animal model investigating the role of the endoplasmic reticulum stress (ERS)-induced apoptosis. Results revealed that RH-MTX-SLNs were in the suitable nanosized range with high negative zeta potential indicating good stability. In-vivo, RH-MTX-SLNs significantly improved all measured inflammatory and arthritic markers, confirmed by electron microscopy and histology examination of the joints. Besides, the formulation was able to alter the ERS-mediated apoptosis. In conclusion, RH-MTX-SLNs can represent a promising therapeutic approach for RA showing significant anti-arthritic activity. Graphical abstract

Modulation of mi-RNA25/Ox-LDL/NOX4 signaling pathway by polyphenolic compound Hydroxytyrosol as a new avenue to alleviate cisplatin-induced acute kidney injury, a mechanistic study in rats - Mohamed Gamal El-Din Ewees; Raha Orfali; Enas Ezzat Rateb; Hossam M. Hassan; Wael N. Hozzein; Dalal Hussien M. Alkhalfah; Haidy Tamer Abo Sree; Fatema El-Zahraa S. Abdel Rahman; Mostafa E. Rateb; Nesreen Ishak Mahmoud (Environmental Toxicology and Pharmacology, 2023)

Tidal harmonics retrieval using GNSS-R dual-frequency complex observations - Mahmoud Rajabi; Mostafa Hoseini; Hossein Nahavandchi; Milad Asgarimehr; Maximilian Semmling; Markus Ramatschi; Mehdi Goli; Jens Wickert (Journal of Geodesy, 2023)
Tidal analysis and methods for estimation and prediction of ocean tidal constitutes are essential in a large area of scientific disciplines, for example, navigation, onshore and offshore engineering, and production of green energy. Ground-based Global Navigation Satellite System-Reflectometry (GNSS-R) has been proposed as an alternative method for measuring sea surface height. We use 6 years of GNSS-R observations at In-phase and Quadrature levels from July 2015 to May 2021 obtained from a dedicated receiver and sea-looking left hand circular polarization antenna for estimating sea level (SL). In the first step, the multivariate least-square harmonic estimation (LS-HE) method is applied for SL estimation. Then, final SL time series are generated by combining estimated SL from all satellites at L1 and L2 frequencies in the averaging step. The 6-year root-mean-square error between GNSS-R L12 sea surface heights and a collocated tide gauge (TG) is 5.8 cm with a correlation of 0.948 for a high temporal resolution of 5 min with 15 min averaging window. Afterward, using the univariate LS-HE, we detect tidal harmonics with periods between 30 min to 1 year. The detection results highlight a good match between GNSS-R and TG. Higher harmonics, i.e., the periods shorter than 3 h, show stronger signatures in GNSS-R data. Finally, we estimate the amplitude and phase of standard tidal harmonics from the two datasets. The results show an overall good agreement between the datasets with a few exceptions.

Seasonal dynamics of phytoplankton in the northern part of Suez Gulf, Egypt - Mostafa El-Sheekh; Mahmoud Abu-Faddan; Atef Abo-Shady; Mohamed Zein Alabdein Nassar; Wagdy Labib (Environmental Monitoring and Assessment, 2023)
This study was conducted to evaluate the seasonal variability of phytoplankton in the northern part of the Gulf of Suez (Suez Bay), considering the contribution of physicochemical parameters of bay water in shaping the dynamics, and eutrophication assessment. Water and phytoplankton samples were collected seasonally at nine stations in the Suez Bay during the period from the winter to autumn of 2012. A total of 423 phytoplankton species were identified, comprised mainly of 224 diatoms, 127 dinoflagellates, 33 cyanophytes, 20 chlorophytes, and 9 euglenophytes; the rest of the species (10 species) belong to other six groups. Of these, 28 species were potentially harmful. The total phytoplankton abundance exhibits a significant seasonal variation, with the autumn being the most fertile season, followed by the winter due to the proliferation of diatom species Thalassionema nitzschioides and Proboscia alata f . gracillima , respectively. While the seasonal species richness indicates that the winter attained the highest number of species, followed by summer. Generally, the major diatom genera were Chaetoceros (16 species), Navicula (15 species), Nitzschia (15 species), and Amphora (14 species), while dinoflagellates were principally composed of the genera Protoperidinium (34 species), and Tripos (26 species). Water temperature, pH, salinity, nitrate, and nitrite were the most important explanatory parameters in regard to phytoplankton abundance and chlorophyll a concentration. In addition, the phytoplankton stability exhibited a significant positive relationship with the mean values of dissolved oxygen and biological oxygen demand and the variability of salinity and phosphate, while a negative relationship was observed with ammonia and nitrite and the variability of nitrate. Based on the trophic index (TRIX), the bay water was classified as mesotrophic (moderately polluted) for almost the entire year except in the autumn as it turned eutrophic. The results explored the potential importance of the environmental heterogeneity in the bay as a key structuring mechanism of phytoplankton abundance and biomass, influenced by anthropogenic activities.

Comparative genome analyses of three serotypes of Lactococcus bacteria isolated from diseased cultured striped jack ( Pseudocaranx dentex ) - Mahmoud Mostafa Mahmoud; Mohamed Abdelsalam; Satoshi Kawato; Shogo Harakawa; Hidemasa Kawakami; Ikuo Hirono; Hidehiro Kondo (Journal of Fish Diseases, 2023)
Lactococcosis, caused by members of the genus Lactococcus , represents a devastating disease inducing mass mortalities and economic losses in many fish species worldwide. The present work aimed to compare the whole genome sequences of three different serotypes of Lactococcus garvieae isolated from diseased cultured striped jack ( Pseudocaranx dentex ) in Ehime prefecture, Japan. The three serotypes showed different virulence in the challenge test using Japanese amberjack ( Seriola quinqueradiata ). The genome sequencing revealed that two of the strains (serotype I and serotype III) were identified as L. garvieae , while the third strain (serotype II) was identified as L. formosensis . The chromosome sizes of the three serotypes ranged from 1.9 to 2.0 Mb; the GC content ranges were 38.2 to 38.9%; and the numbers of predicted protein‐coding sequences (CDSs) were from 1922 to 1959. Only the serotype II harbours two plasmids, sizes of around 14 kb and 9 kb. The detected virulence factors varied among the different serotypes with some shared factors like adherence, anti‐phagocytosis, secretion system, toxin (haemolysin), serum resistance, antimicrobial resistance and others. The genomes also contained factors responsible for resistance to toxic compounds. The genome of the serotype III tended to encode more prophage regions than the other serotypes.

The simultaneous degradation of prochloraz and tebuconazole in water with monitoring their degradation products using liquid chromatography-tandem mass spectrometry - Mahmoud M. Awwad; Sherif M. Taha; Mostafa M.H. Khalil; Abdelnaby Mohamed Salem; Jean-Marc Chovelon (Environmental Science and Pollution Research, 2023)

Chemical constituents from Colchicum palaestinum (Baker) C. Archer with the assessment of its antioxidant, wound scratch, and tyrosinase repressive potential - Mostafa A. Asmaey; Maha M. Salem; Mahmoud Emam; Mona O.El Shabrawy; Sameh R. Hussein; Ibrahim A. El Garf; Mona M. Marzouk; Nektarios Aligiannis; Mai M. Farid (South African Journal of Botany, 2023)

Immunostimulant potential of Moringa Oleifera leaves alcoholic extract versus Oregano Essential Oil (OEO) against cyclophosphamide-induced immunosuppression in broilers chicks - Mostafa Abdelgaber Mohamed; Amany Abdelbaky El-Mleeh; Rania Talat Hamad; Ibrahim Said Abu-Alya; Mohamed Hamdy El-Hewaity; Ahmed Ragab Elbestawy; Abdelrahman Mahmoud Elbagory; Ahmed Saber Sayed-Ahmed; Mabrouk Attia Abd Eldaim; Omnia Ibrahim Elshabrawy (Tropical Animal Health and Production, 2023)
The current study was conducted to evaluate the immunoenhancement effect of Moringa oleifera leaves alcoholic extract (MOLE) versus Oregano essential oil (OEO) against cyclophosphamide induced immunosuppression in broilers chicks. A total of a three hundred one-day-old chicks were assigned randomly into three main dietary groups, control, MOLE, and OEO for 14 days. After 14 days the three main experimental groups were subdivided into six groups, control, cyclophosphamide, MOLE, MOLE and Cyclophosphamide, OEO, and OEO and cyclophosphamide. Each group of these six groups was subdivided into three subgroups. Supplementation of broiler chicks with MOLE and OEO for 14 days significantly increased body weight compared to the control group. However, injection of broiler chicks with cyclophosphamide significantly induced body weight loss, impaired immunological response represented by decreasing total leukocytic count, differential leukocytic count, phagocytic activity, phagocytic index, and hemagglutinin inhibition titer for New Castle disease virus, lymphoid organs depletion, and increased the mortality rate. In contrast, supplementation of cyclophosphamide treated chicks with MOLE and OEO significantly reduced cyclophosphamide induced body weight loss and impaired immunological responses, as it showed significant increase in body weight, total leukocytic count, differential leukocytic count, phagocytic activity, phagocytic index, and hemagglutinin inhibition titer for New Castle disease virus, lymphoid organs proliferation, and reduced the mortality rate. This study indicated that MOLE and OEO supplementation ameliorated cyclophosphamide induced body weight loss and impaired immunological responses.

Spirulina platensis-Inoculated Humified Compost Boosts Rhizosphere Soil Hydro-Physico-Chemical Properties and Atriplex nummularia Forage Yield and Quality in an Arid Saline Calcareous Soil - Sameera A. Alghamdi; Hesham F. Alharby; Mahmoud A. Abdelfattah; Ibrahim A. A. Mohamed; Khalid R. Hakeem; Mostafa M. Rady; Ahmed Shaaban (Journal of Soil Science and Plant Nutrition, 2023)

Paleoenvironmental contribution and visual kerogen assessment of some Upper Cretaceous sediments from southern Egypt - Magdy Salah Mahmoud; Miran Mostafa Khalaf (Arabian Journal of Geosciences, 2023)
We investigated the palynological organic matter (POM) recovered from shale horizons, intercalating the Nubian-type sandstones in middle Egypt, for paleoenvironmental reconstruction. Our palynofacies are dominated by either amorphous organic matter (AOM) or phytoclasts whereas palynomorphs are relatively rare, but not uncommon. The palynofacies categories revealed two different palynofacies types, reflecting estuarine/tidal and fluvio-lacustrine environments for the Maghrabi and the basal Quseir formations, respectively. The kerogen composition of our investigated material and the colors of the thin-walled spores suggest possible sources of hydrocarbons, which are poorly explored in the middle and southern areas of Egypt. Our findings confirmed the previously described marine origin of the Maghrabi Formation. The complete missing of any marine palynomorphs suggests that the basal sediments of the Quseir Formation are almost exclusively of terrestrial origin. This may reveal that the worldwide Late Cretaceous transgression was not effective during deposition of these basal clastics.

Systemic Management of Water Resources with Environmental and Climate Change Considerations - Behnam Sadeghi; Mahmoud Ahmadpour Borazjani; Mostafa Mardani; Saman Ziaee; Hamid Mohammadi (Water Resources Management, 2023)

RPTRF: A rapid perfect tandem repeat finder tool for DNA sequences - Reza Behboudi; Mostafa Nouri-Baygi; Mahmoud Naghibzadeh (BioSystems, 2023)

Geochemical characteristics of natural gases and source rocks in Obayied sub-basin, north Western Desert, Egypt: implications for gas-source correlation - Mostafa Hassan; Mahmoud Leila; Mohammed Ahmed; Ghalib Issa; Omar Hegab (Acta Geochimica, 2023)

Stratigraphic influences on reservoir heterogeneities of the Mid-Cretaceous carbonates in southwest Iran: Insight from an integrated stratigraphic, diagenetic and seismic attribute study - Mostafa Sabouhi; Reza Moussavi-Harami; Ali Kadkhodaie; Payman Rezaee; Mahmoud Jalali; David A. Wood (Journal of Asian Earth Sciences, 2023)

Magnetic Signature of Gold Deposits: Example from Um Garayat Region, South Eastern Desert, Egypt - Mohamed Mostafa Gobashy; Mahmoud M. Mekkawi; Sultan Awad Sultan Araffa; Moahmed M. Ezz Eldin; Mohamed Hassan Khalil (Pure and Applied Geophysics, 2023)
Magnetic methods of exploration have proved to be efficient and have potential in the gold mineralization industry. New magnetic processing technologies aid in improving the process of interpretation and gold opportunity identification. In this work, we show the possible application of combined digital magnetic filters to explore new gold mineralization localities with application to a well-known Au mineralization zone. Um Garayat (UG) region, southeastern desert, Egypt, is an ancient example of a potential area for gold mining. Modern analysis showed that other types of mineral concentrations are present. So, exploiting the magnetic signature of the area for future investment is of great interest. The old UG gold mine is characterized by volcanic and tectonic features such as faulting and folding that affect the arc sedimentary rock sequence of repeated deformation stages. A thorough geophysical effort has been carried out around the old gold mine in the UG area to explore the extension of mineralized ore deposits. A detailed geophysical survey using magnetics was carried out in this study together with the available aeromagnetic data. Field data sets on appropriate sites were measured, processed, and evaluated by suitable software. High magnetic anomalies were detected based on grid filter analysis and contact occurrence maps as marked as possible ore deposits after satisfying the geologic conditions for gold formation. An integrated understanding of attained results revealed that the new possible ore deposits are related directly to fault and fracture zones in the shape of lenses of variable thickness in this zone. Results show that newly detected mineral occurrences in the UG area are also controlled by major faults and hydrothermal solution enrichment along fault zones at a depth ranging from 20 to 70 m. Favorable fault/joint mineralized places were located. The relationship between the Au-quartz vein's strike direction compared with magnetic anomaly lineament analysis was studied. Search for new sources of Au and other mineral deposits in addition to quartz veins is needed as pockets of accumulated mineral-rich rock fragments are deposited in drainage wadis and fault/joint zones because of hydrothermal solution enrichment.

Self-propelled nanojets an interfacial Schottky junctions modulated oxygen vacancies enriched for enhanced photo-Fenton degradation of organic contaminant: Improving H2O2 generation, Fe3+/Fe2+ cycle and enhancing plant metabolism - S. Balasurya; Mohammad K. Okla; Hamada AbdElgawad; Abdullah A. AL-ghamdi; Mostafa A. Abdel-Maksoud; Saud S. Al-Amri; Mahmoud M.Y. Madany; S. Sudheer Khan (Chemosphere, 2023)

Machine learning modeling of polycarbonate ultrafiltration membranes at different temperatures, Al2O3 nanoparticle volumes, and water ratios - Sasan Zahmatkesh; Mahmoud Kiannejad Amiri; Seyed Peiman Ghorbanzade Zaferani; Mohammad Reza Sarmasti Emami; Mostafa Hajiaghaei-Keshteli; Munirah D. Albaqami; Ammar Mohamed Tighezza; Maryam Shafahi; Ning Han (Chemosphere, 2023)

Sunlight promoted self-fenton photodegradation and pathway of doxycycline: Interactive effects of nanomaterial on bean plant and its genotoxicity against Allium cepa - S. Balasurya; Mohammad K. Okla; Hamada AbdElgawad; Abdullah A. AL-ghamdi; Mostafa A. Abdel-Maksoud; Saud S. Al-Amri; Mahmoud M.Y. Madany; S. Sudheer Khan (Chemosphere, 2023)

Whole-genome sequencing (WGS) analysis of Brucella suis biovar 2 isolated from domestic pigs in Egypt for epidemiological and genetic diversity tracing - Gamal Wareth; Nour H. Abdel-Hamid; Mahmoud E.R. Hamdy; Walid Elmonir; Eman I.M. Beleta; Mohamed El-Diasty; Mostafa Y. Abdel-Glil; Falk Melzer; Heinrich Neubauer (Veterinary Microbiology, 2023)

Comparative Study of Different Discrete Wavelet Based Neural Network Models for long term Drought Forecasting - Djerbouai Salim; Souag-Gamane Doudja; Ferhati Ahmed; Djoukbala Omar; Dougha Mostafa; Benselama Oussama; Hasbaia Mahmoud (Water Resources Management, 2023)

Studying the effect of contaminated asphalt pavement surfaces on skid resistance - Ahmed Abdelghani Mahmoud; Ahmed AbdELazim M.Ali; Abdelzaher E. A. Mostafa; Mokhtar F. Ibrahim (Innovative Infrastructure Solutions, 2023)

Formal verification confirms the role of p53 protein in cell fate decision mechanism - Eman Abdelaziz Mahmoud; Mostafa Herajy; Ibrahim E. Ziedan; Hazem I. Shehata (Theory in Biosciences, 2023)
The bio-cell cycle is controlled by a complex biochemical network of signaling pathways. Modeling such challenging networks accurately is imperative for the understanding of their detailed dynamical behavior. In this paper, we construct, analyze, and verify a hybrid Petri net (HPN) model of a complex biochemical network that captures the role of an important protein (namely p53) in deciding the fate of the cell. We model the behavior of the cell nucleus and cytoplasm as two stochastic and continuous Petri nets, respectively, combined together into a single HPN. We use simulative model checking to verify three different properties that capture the dynamical behavior of p53 protein with respect to the intensity of the ionizing radiation (IR) to which the cell is exposed. For each IR dose, 1000 simulation runs are carried out to verify each property. Our verification results showed that the fluctuations in p53, which relies on IR intensity, are compatible with the findings of the preceding simulation studies that have previously examined the role of p53 in cell fate decision.

Cytotoxic and antileishmanial triterpenes of Tabebuia aurea (Silva Manso) leaves - Amany Hamouda Mahmoud; Basma Khalaf Mahmoud; Mamdouh Nabil Samy; Mostafa Ahmad Fouad; Mohamed Salah Kamel; Katsuyoshi Matsunami (Natural Product Research, 2022)

Carvedilol ameliorates dexamethasone-induced myocardial injury in rats independent of its action on the α1-adrenergic receptor - Rasha M. S. M. Mohamed; Enssaf Ahmad Ahmad; Bothina H. F. Omran; Amr T. Sakr; Islam A. A. E.-H. Ibrahim; Mona F. Mahmoud; Mostafa E. El-Naggar (Naunyn-Schmiedeberg's Archives of Pharmacology, 2022)
The current study aimed to investigate the cardiotoxic effect of dexamethasone-high-dose in rats, the therapeutic effect of carvedilol and the role of α1-adrenergic receptor (α1AR). The experiment involved 6 groups: control, dexamethasone (10 mg/kg), carvedilol (10 mg/kg), phenylephrine (1 mg/kg), phenylephrine plus carvedilol and propranolol (30 mg/kg). Drugs and vehicles were given for 7 days. Dexamethasone was given with the drugs in the last 4 groups. On the 8 th -day and after overnight fasting, serum and cardiac samples were collected. Serum levels of cardiac troponin I and creatine kinase–myoglobin as well as cardiac levels of diacylglycerol, malondialdehyde, kinase activity of Akt, transforming growth factor-β, Smad3 and alpha smooth muscle actin were measured. Cardiac samples were also used for histopathological examination using hematoxylin–eosin and Sirius red stains, in addition to immunohistochemical examination using β-arrestin2 antibody. Dexamethasone induced cardiac injury via increasing oxidative stress, apoptosis and profibrotic signals. Carvedilol significantly reduced the dexamethasone-induced cardiotoxicity. Using phenylephrine, a competitive α1-agonist, with carvedilol potentiated the cardioprotective actions of carvedilol. Propranolol, a β-blocker without activity on α1ARs, showed higher cardiac protection than carvedilol. Dexamethasone-high-dose upregulates cardiac oxidative stress, apoptotic and profibrotic signals and induces cardiac injury. Blocking the α1-adrenergic receptor by carvedilol attenuates its cardioprotective effects against dexamethasone-induced cardiotoxicity.

Epidemiology, clinical features, and treatment modalities of facial nerve palsy in COVID-19 patients: a systematic review - Aya Turki; Kirellos Said Abbas; Abdelrahman M Makram; Mostafa Elfert; Mahmoud Elmarabea; Nahla Ahmed El-Shahat; Hassan Abdalshafy; Akua Sampong; Sirisha Chintalapati; Nguyen Tien Huy (Acta Neurologica Belgica, 2022)

Combined Effect of Prickly Pear Waste Biochar and Azolla on Soil Fertility, Growth, and Yield of Roselle (Hibiscus sabdariffa L.) Plants - Hassan M. Al-Sayed; Ahmed M. Ali; Mahmoud A. Mohamed; Mostafa F. Ibrahim (Journal of Soil Science and Plant Nutrition, 2022)
Although the use of biochar to promote plant growth has been reported by many researchers, the combined effect of prickly pear waste biochar (BC) and Azolla (AZ) in a field experiment on the roselle plants did yet receive attention. Therefore, the study aims to evaluate the effect of biochar and Azolla extract on the growth, production, and quality of roselle plants. The experiment treatments were in a completely randomized block design with three replicates. Biochar was added at rates of 0, 10, and 20 ton ha −1 and AZ was applied at rates of 0, 3, and 6% in addition to a control treatment. Biochar added at high rate (20 ton ha −1 ) significantly increased the fresh and dry weights of sepals by 27.98 and 35.73%, respectively, compared to the control. The corresponding values were significantly increased by 11.89 and 11.85% over the control when Azolla was added at rate of 6%. The interaction effect of both BC and AZ treatments at high rate significantly increased the fresh and dry weight of sepals by 47.16 and 60.59%, respectively, compared to the control. The interaction effect of BC and AZ realized significant effect on soil properties, growth and yield, as well as pigments of roselle plants. This is a good evident means that BC and AZ applications separately or combined are considered promising materials for sustainable organic agriculture and safety food.

Cytotoxicity and chemical profiling of the Red Sea soft corals Litophyton arboreum - Amany Hamouda Mahmoud; Sabry A. H. Zidan; Mamdouh Nabil Samy; Abdallah Alian; Usama Ramadan Abdelmohsen; Mostafa Ahmed Fouad; Mohamed Salah Kamel; Katsuyoshi Matsunami (Natural Product Research, 2022)

Modeling COVID-19 effects on SDGs using system dynamics in Egypt - Mohamed Marzouk; Shimaa Azab; Nehal Elshaboury; Alaa Megahed; Mahmoud Metawie; Mostafa El Hawary; Doaa Ghaith; AbdElMoniem Bayoumi (Environmental Science and Pollution Research, 2022)
The coronavirus disease 2019 (COVID-19) poses a significant threat to achieving the Sustainable Development Goals (SDGs). To address this challenge, a thorough examination of the pandemic’s influence on four SDGs in Egypt is presented in a system dynamic model. The addressed goals are related to no poverty (SDG 1), zero hunger (SDG 2), decent work and economic growth (SDG 8), and climate action (SDG 13). The model is simulated over 35 years extending from 2015 to 2050. Furthermore, a web-based interactive learning environment is developed to analyze the interdependencies among public health activities and study the impacts of possible intervention countermeasures or prevention policies. Indicators including poverty line, food insecurity, gross domestic product (GDP) growth rate, and greenhouse gas (GHG) emissions are evaluated to track Egypt’s performance in relation to SDGs 1, 2, 8, and 13. According to the simulation model, the poverty line will continue to decline until it reaches around 16% by 2050. According to the significant governmental efforts to follow its vision of 2030, Egypt can achieve a decreasing percentage of food insecurity, reaching 3% in 2030, and this percentage will continue to decrease until it reaches full sufficiency by 2050. The GDP growth rate will rise every year until it reaches 13.71% in 2050. With respect to climate, GHG emissions are predicted to fall to roughly 97 Mt CO2-equivalents by 2050. This approach revitalizes debates about the achievement of SDGs amid the crisis and acts as a powerful tool that aids decision-makers in identifying leverage points to avoid the long-term negative repercussions of the crisis on the economy, people, and environment.

Anticancer activity of chicken cathelicidin peptides against different types of cancer - Maged Mostafa Mahmoud; Modhi Alenezi; Ahmed M. Al-Hejin; Turki S. Abujamel; Fadwa Aljoud; Abdulwahab Noorwali; Ibrahim A. Awad; Mohammed Alkhaled; Haitham A. Yacoub (Molecular Biology Reports, 2022)

In vivo study of dose-dependent antioxidant efficacy of functionalized core–shell yttrium oxide nanoparticles - Samr Kassem; Mahmoud M. Arafa; Manal M. Yehya; Mostafa A. M. Soliman (Naunyn-Schmiedeberg's Archives of Pharmacology, 2022)
Herein, we assess the dose-dependent antioxidant efficacy of ultrafine spherical functionalized core–shell yttrium oxide nanoparticles (YNPs) with a mean size of 7–8 nm and modified with poly EGMP (ethylene glycol methacrylate phosphate) and N-Fluorescein Acrylamide. The antioxidant properties of these nanoparticles were investigated in three groups of Sprague–Dawley rats (10 per group) exposed to environmental stress daily for 1 week and one control group. Groups 2 and 3 were intravenously injected twice a week with YNPs at 0.3 and 0.5 mg at 2nd and 5th day of environmental stress exposure respectively. Different samples of blood and serum were collected from all experimental groups at end of the experiment to measure oxidative biomarkers such as total antioxidant capacity (TAC), hydroxyl radical antioxidant capacity (HORAC), oxygen radical antioxidant capacity (ORAC), malondialdehyde (MDA), and oxidants concentration as hydrogen peroxide (H 2 O 2 ). The liver, brain, and spleen tissues were collected for fluorescence imaging and histopathological examination in addition to brain tissue examination by transmission electron microscope (TEM). Inductively coupled plasma-mass spectrometry (ICP-MS) was used to estimate YNPs translocation and concentration in tissues which is consecutively dependent on the dose of administration. Depending on all results, poly EGMP YNPs (poly EGMP yttrium oxide nanoparticles) can act as a potent direct antioxidant in a dose-dependent manner with good permeability through blood–brain barrier (BBB). Also, the neuroprotective effect of YNPs opening the door to a new therapeutic approach for modulating oxidative stress–related neural disorders. Highlights • The dose-dependent antioxidant efficacy of ultrafine spherical functionalized core–shell yttrium oxide nanoparticles (YNPs) with a mean size of 7–8 nm and modified with poly EGMP (ethylene glycol methacrylate phosphate) and N-Fluorescein Acrylamide was assessed. • The dose of administration directly affecting the brain, liver, and spleen tissues distribution, retention, and uptake of YNPs and direct correlation between the absorbed amount and higher dose administered. • YNPs can act as a potent direct antioxidant in a dose-dependent manner with good permeability through blood–brain barrier (BBB). Graphical abstract

The Fluorescent Effect of Withania Somnifera Chitosan Nanocomposite as an Effective Contrast Agent for Cancer Theragnostic: Experimental Study in Vitro - Hala S. Abuelmakarem; Mahmoud A. Sliem; Jala El-Azab; Mostafa Farghaly; M.A. Om-Hashem; Wafaa A. Ahmed (Journal of Fluorescence, 2022)

In-silico screening of naturally derived phytochemicals against SARS-CoV Main protease - Islam Mostafa; Nashwa Hashem Mohamed; Basant Mohamed; Rafa Almeer; Mahmoud M. A. Abulmeaty; Simona G. Bungau; Assem Mohamed El-Shazly; Galal Yahya (Environmental Science and Pollution Research, 2022)

Vitamin D Receptor Gene Polymorphisms and Risk of Knee Osteoarthritis: Possible Correlations with TNF-α, Macrophage Migration Inhibitory Factor, and 25-Hydroxycholecalciferol Status - Mohammed H. Hassan; Amer Alkot Mostafa Elsadek; Marwa Ahmed Mahmoud; Bakheet E. M. Elsadek (Biochemical Genetics, 2022)

Establishing a Marine Gravity Database around Egypt from Satellite Altimetry-Derived and Shipborne Gravity Data - Ahmed Zaki; Mahmoud Magdy; Mostafa Rabah; Ahmed Saber (Marine Geodesy, 2022)

Microwave-assisted green synthesis of silver nanoparticles using Annona squamosa peels extract: characterization, antioxidant, and amylase inhibition activities - Abdel-Moniem S. Hassan; AboBaker S. Mahmoud; Mohamed Fawzy Ramadan; Mostafa A. Eissa (Rendiconti Lincei. Scienze Fisiche e Naturali, 2022)

Scrutinizing the Feasibility of Nonionic Surfactants to Form Isotropic Bicelles of Curcumin: a Potential Antiviral Candidate Against COVID-19 - Dina B. Mahmoud; Mohamed Mofreh Bakr; Ahmed A. Al-karmalawy; Yassmin Moatasim; Ahmed El Taweel; Ahmed Mostafa (AAPS PharmSciTech, 2021)
Investigating bicelles as an oral drug delivery system and exploiting their structural benefits can pave the way to formulate hydrophobic drugs and potentiate their activity. Herein, the ability of non-ionic surfactants (labrasol ® , tween 80, cremophore EL and pluronic F127) to form curcumin loaded bicelles with phosphatidylcholine, utilizing a simple method, was investigated. Molecular docking was used to understand the mechanism of bicelles formation. The % transmittance and TEM exhibited bicelles formation with labrasol ® and tween 80, while cremophor EL and pluronic F127 tended to form mixed micelles. The surfactant-based nanostructures significantly improved curcumin dissolution (99.2 ± 2.6% within 10 min in case of tween 80-based bicelles) compared to liposomes and curcumin suspension in non-sink conditions. The prepared formulations improved curcumin ex vivo permeation over liposomes and drug suspension. Further, the therapeutic antiviral activity of the formulated curcumin against SARS-CoV-2 was potentiated over drug suspension. Although both Labrasol ® and tween 80 bicelles could form bicelles and enhance the oral delivery of curcumin when compared to liposomes and drug suspension, the mixed micelles formulations depicted superiority than bicelles formulations. Our findings provide promising formulations that can be utilized for further preclinical and clinical studies of curcumin as an antiviral therapy for COVID-19 patients.

Hepatoprotective Effect of Alcoholic and N-hexane Extracts of Crayfish Procambarus Clarkii against CCl 4 -induced Damage in HepG2 Cells - Mostafa Ahmed Shaban; Ahmed A. El-Husseiny; Hesham Mohamed Shaban; Salwa Abdel Hamid Hamdi; Mostafa Mahmoud Elshafey (Journal of Aquatic Food Product Technology, 2021)

Local anaesthetic potential, metabolic profiling, molecular docking and in silico ADME studies of Ocimum forskolei , family Lamiaceae - Eman Maher Zahran; Usama Ramadan Abdelmohsen; Mahmoud. M. Shalash; M. Alaraby Salem; Hany Ezzat Khalil; Samar Yehia Desoukey; Mostafa Ahmed Fouad; Markus Krischke; Martin Mueller; Mohamed Salah Kamel (Natural Product Research, 2021)

Aluminum sulfate regeneration from surface water treatment waste in Cairo, Egypt - Mahmoud M. Fouad; Ahmed S. El-Gendy; Mostafa M. H. Khalil; Taha M. A. Razek (Environmental Science and Pollution Research, 2021)

Investigating habitat degradation of Ursus arctos using species distribution modelling and remote sensing in Zagros Mountains of Iran - Seyed Pouya Hosseini; Reza Jafari; Mostafa Tarkesh Esfahani; Josef Senn; Mahmoud-Reza Hemami; Mohadeseh Amiri (Arabian Journal of Geosciences, 2021)

Chemical and bacterial quality monitoring of the Nile River water and associated health risks in Qena–Sohag sector, Egypt - Mahmoud A. Abdelhafiz; Ahmed A. Elnazer; El-Montser M. Seleem; Alaa Mostafa; Ahmed G. Al-Gamal; Salman A. Salman; Xinbin Feng (Environmental Geochemistry and Health, 2021)

Beneficial effects of vitamin D on anxiety and depression-like behaviors induced by unpredictable chronic mild stress by suppression of brain oxidative stress and neuroinflammation in rats - Hossein Bakhtiari-Dovvombaygi; Saeed Izadi; Mostafa Zare Moghaddam; Milad Hashemzehi; Mahmoud Hosseini; Hassan Azhdari-Zarmehri; Hossein Dinpanah; Farimah Beheshti (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Treatment of hepatitis C virus infection with direct-acting antivirals plus ribavirin eliminates viral RNA from peripheral blood mononuclear cells and reduces virologic relapse in diverse hepatic parenchymal changes - Mohamed Darwish Ahmed Abd Alla; Reham M. Dawood; Hassan Abd EL-Hafeth Rashed; Galal Farrag; Islam Abdelmawla Emran Ammar; Mohamed Mahmoud Abdel-Halim Mahmoud; Ghada M. Salum; Ahmed Mohamed Abdulhamid Altanbouly; Mai A. El Meguid; Mostafa K. El Awady (Archives of Virology, 2021)

Synthesis of 3,3′-methylenebis(4-hydroxyquinolin-2(1H)-ones) of prospective anti-COVID-19 drugs - Ashraf A. Aly; Alaa A. Hassan; Asmaa H. Mohamed; Esraa M. Osman; Stefan Bräse; Martin Nieger; Mahmoud A. A. Ibrahim; Sara M. Mostafa (Molecular Diversity, 2021)

Assessment of NRCAN PPP online service in determination of crustal velocity: case study Northern Egypt GNSS Network - Nadia AbouAly; Mahmoud Elhussien; Mostafa Rabah; Zaki Zidan (Arabian Journal of Geosciences, 2021)

Land deformation monitoring by GNSS in the Nile Delta and the measurements analysis - Nadia AbouAly; Mahmoud Hussien; Mostafa Rabah; Zaki Zidan; Mohamed Saleh (Arabian Journal of Geosciences, 2021)

RETRACTED ARTICLE: Protective effect of cerium oxide nanoparticles on cisplatin and oxaliplatin primary toxicities in male albino rats - Amira Mohamed Abdelhamid; Shireen Sami Mahmoud; Aziza E. Abdelrahman; Nelly Mohamed Said; Mostafa Toam; Walaa Samy; Marwa AbdEl-Moniem Amer (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Synthesis of core–shell activated carbon/CaO composite from Ficus Nitida leaves, as an efficient adsorbent for removal of methylene blue - Mostafa M. Emara; Rabie Saad Farag; Mahmoud F. Mubarak; Sayed Kotb Ali (Nanotechnology for Environmental Engineering, 2020)

Biosurfactant electrospun nanofibers exhibit minimal side effects on the structure and function of the liver tissue in male rat model - Hossam Abd Rabou Ebaid; Ahmed Abdel-Mageed; Jameel Homoud Al-Tamimi; Iftekhar Hassan; Ahmed Mostafa Rady; Mohamed Hassan El-Newehy; Ashraf Mohamed Mashaly; Ahmed AbdelFattah Mahmoud Abdel-Megeed; Ibrahim Alhazza; Essam Sayed Abdel-Halim; Abdelfattah Zeidan Mohamed Salem (Environmental Science and Pollution Research, 2020)

Molecular characterization and genetic diversity of the infectious laryngotracheitis virus strains circulating in Egypt during the outbreaks of 2018 and 2019 - Mahmoud Bayoumi; Mohamed El-Saied; Haitham Amer; Mostafa Bastami; Ezz Eldein Sakr; Magdy El-Mahdy (Archives of Virology, 2020)

Folic acid and flaxseed oil supplements in Ossimi ewes: effect on body weight changes, progesterone profile, blood chemistry, and litter traits - Mahmoud S. El-Tarabany; Mostafa A. Atta; Sana S. Emara; Mohamed M. Mostafa (Tropical Animal Health and Production, 2020)

Techno-economic estimation of electroplating wastewater treatment using zero-valent iron nanoparticles: batch optimization, continuous feed, and scaling up studies - Ahmed Hamdy; Mohamed K. Mostafa; Mahmoud Nasr (Environmental Science and Pollution Research, 2019)

HIV/AIDS-related stigma and discrimination among health care workers at Tanta University Hospitals, Egypt - Ibrahim Ali Kabbash; Ehab A. Abo Ali; Mostafa Mahmoud Elgendy; Mostafa Mohamed Abdrabo; Helal Mohamed Salem; Mohammed Ramadan Gouda; Yousef Saleh Elbasiony; Nader Elboshy; Mohammed Hamed (Environmental Science and Pollution Research, 2018)

Optimization and Characterization of Thymoquinone-Loaded Liposomes with Enhanced Topical Anti-inflammatory Activity - Mahmoud Mostafa; Eman Alaaeldin; Usama Farghaly Aly; Hatem A. Sarhan (AAPS PharmSciTech, 2018)

Trichosporon jirovecii infection of red swamp crayfish ( Procambarus clarkii ) - Ebtsam Sayed Hassan Abdallah; Mahmoud Mostafa Mahmoud; Ismail Ramadan Abdel‐Rahim (Journal of Fish Diseases, 2018)
One hundred and twenty‐nine isolates of Trichosporon jirovecii were isolated from the melanized exoskeleton as well as eyestalks, gills, muscle and haemolymph of red swamp crayfish ( Procambarus clarkii ) collected from the River Nile, during summer 2015. Isolates were similar morphologically, biochemically and genetically. Also, random amplified polymorphic DNA (RAPD) analysis exhibited no polymorphism among the tested isolates. Virulence factors such as chitinase, protease, lipase activities and biofilm formation were examined. Challenge test, using a representative isolate (Tj_ASU8), proved its pathogenicity against crayfish. Magnesium oxide nanoparticles had a good antifungal activity with a minimum fungicidal concentration of 8 mg/ml. To the best of our knowledge, this is the first report for isolation of T. jirovecii from red swamp crayfish, showing melanization, from the River Nile. We assume that infected crayfish may act as a vector for this fungus and can disseminate infection to all susceptible hosts in the vicinity.

Efficacy analysis of hydroxychloroquine therapy in systemic lupus erythematosus: a study on disease activity and immunological biomarkers - Seyed Mostafa Monzavi; Aida Alirezaei; Zhaleh Shariati-Sarabi; Jalil Tavakol Afshari; Mahmoud Mahmoudi; Banafsheh Dormanesh; Faezeh Jahandoost; Ali Reza Khoshdel; Ali Etemad Rezaie (Inflammopharmacology, 2018)

Appraisal of Moringa oleifera crude proteins for the control of root-knot nematode, Meloidogyne incognita in banana - Mostafa S. M. El-Ansary; Mahmoud A. Al-Saman (Rendiconti Lincei. Scienze Fisiche e Naturali, 2018)

Stop eating plastic, molecular signaling of bisphenol A in breast cancer - Ayman Shafei; Marwa Matbouly; Ezzat Mostafa; Salah Al Sannat; Mahmoud Abdelrahman; Bola Lewis; Badr Muhammad; Shaima Mohamed; Randa Mohamed Mostafa (Environmental Science and Pollution Research, 2018)

Effectiveness of different avian influenza (H5) vaccination regimens in layer chickens on the humoral immune response and interferon-alpha signalling immune marker - Mustafa Hamad; Omar Amen; Mohamed Mahmoud; Ola Hassanin; Mostafa Saif-Edin (Veterinary Research Communications, 2018)

Selectivity Improvement for Spectrofluorimetric Determination of Oseltamivir Phosphate in Human Plasma and in the Presence of Its Degradation Product - Mahmoud A. Omar; Sayed M. Derayea; Islam M. Mostafa (Journal of Fluorescence, 2017)

Bioactive/Natural Polymeric Scaffolds Loaded with Ciprofloxacin for Treatment of Osteomyelitis - Amany A. Mostafa; Mayyada M. H. El-Sayed; Azza A. Mahmoud; Amira M. Gamal-Eldeen (AAPS PharmSciTech, 2017)

Biological characterization of highly pathogenic avian influenza H5N1 viruses that infected humans in Egypt in 2014-2015 - Rabeh El-Shesheny; Ahmed Mostafa; Ahmed Kandeil; Sara H. Mahmoud; Ola Bagato; Amel Naguib; Samir El Refaey; Richard J. Webby; Mohamed A. Ali; Ghazi Kayali (Archives of Virology, 2017)

Physiological and lactation responses of Egyptian dairy Baladi goats to natural thermal stress under subtropical environmental conditions - Mahmoud S. El-Tarabany; Akram A. El-Tarabany; Mostafa A. Atta (International Journal of Biometeorology, 2017)

An application of genetics-chemicals constituents to the relatedness of three Euphorbia species - Mahmoud Moustafa; Osama Mostafa; Dema Al-Shahrani; Sulaiman Alrumman (Biologia, 2016)

The multi-kinase inhibitor pazopanib targets hepatic stellate cell activation and apoptosis alleviating progression of liver fibrosis - Mahmoud Elshal; Nashwa Abu-Elsaad; Amr El-Karef; Tarek Mostafa Ibrahim (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

Perinatal transmission of hepatitis C antigens: envelope 1, envelope 2 and non-structural 4 - Abdelfattah M. Attallah; Sanaa O. Abdallah; Mohamed El-Far; Mohamed M. Omran; Ashraf A. Tabll; Mohamed F. Ghaly; Said M. Ezzat; Manal O. Elhamshary; Zeinab M. El-Gohary; Attiya H. Mohamedin; Adel A. El-Morsi; Ahmed A. Askora; et al. (Infectious Diseases, 2015)

Modification of Hippocampal Markers of Synaptic Plasticity by Memantine in Animal Models of Acute and Repeated Restraint Stress: Implications for Memory and Behavior - Shaimaa Nasr Amin; Ahmed Amro El-Aidi; Mohamed Mostafa Ali; Yasser Mahmoud Attia; Laila Ahmed Rashed (NeuroMolecular Medicine, 2015)

Application of the two dimensional geoelectric imaging technique to explore shallow groundwater in wadi El Gerafi basin, Eastern Central Sinai – Egypt - Hussein Hosni Mahmoud; Mostafa Said M. Barseem; Ahmed Mohamed A. Youssef (Arabian Journal of Geosciences, 2015)

Cilostazol Determination by the Enhancement of the Green Emission of Tb3+ Optical Sensor - M. S. Attia; W. H. Mahmoud; A. O. Youssef; M. S. Mostafa (Journal of Fluorescence, 2011)

Erratum to: Spectrofluorimetric Assessment of Doxycycline Hydrochloride in Pharmaceutical Tablets and Serum Sample Based on the Enhancement of the Luminescence Intensity of the Optical Sensor Sm3+ Ion - M. S. Attia; W. H. Mahmoud; M. N. Ramsis; L. H. Khalil; A. M. Othman; S. G. Hashem; M. S. Mostafa (Journal of Fluorescence, 2011)

Spectrofluorimetric Assessment of Doxycycline Hydrochloride in Pharmaceutical Tablets and Serum Sample Based on the Enhancement of the Luminescence Intensity of the Optical Sensor Sm3+ Ion - M. S. Attia; W. H. Mahmoud; M. N. Ramsis; L. H. Khalil; A. M. Othman; S. G. Hashem; M. S. Mostafa (Journal of Fluorescence, 2011)

Aqueous extract of lavender (Lavandula angustifolia) improves the spatial performance of a rat model of Alzheimer’s disease - Masoud Soheili Kashani; Mostafa Rezaei Tavirani; Sayyed Alireza Talaei; Mahmoud Salami (Neuroscience Bulletin, 2011)

The Spectrum of Fungal Infections with a Special Reference to Dermatophytoses in the Capital Area of Kuwait During 2000–2005: A Retrospective Analysis - Mostafa A. Yehia; Tarek S. El-Ammawi; Khairia M. Al-Mazidi; Mahmoud A. Abu El-Ela; Hejab S. Al-Ajmi (Mycopathologia, 2010)

Novel multicomponent reactions involving isoquinoline or phenanthridine and activated acetylenic ester in the presence of heterocyclic NH or 1,3-dicarbonyl compounds - Mahmoud Nassiri; Malek Taher Maghsoodlou; Reza Heydari; Sayyed Mostafa Habibi Khorassani (Molecular Diversity, 2008)

Synthesis of oxime phosphoranes from reaction between triphenylphosphine and acetylenic esters in the presence of oxime derivatives - Malek Taher Maghsoodlou; Sayyed Mostafa Habibi-Khorassani; Reza Heydari; Asadollah Hassankhani; Ghasem Marandi; Mahmoud Nassiri; Elaheh Mosaddeg (Molecular Diversity, 2007)

Stratigraphy and microfacies of the oligocene sequence at Gabal Bu Husah, Marada Oasis, South Sirte Basin, Libya - Mostafa M. Imam; Mahmoud A. Galmed (Facies, 2000)

Mobilization of soil and fertilizer phosphate by cover crops - Mahmoud Kamh; Walter J. Horst; Fathi Amer; Hamida Mostafa; Peter Maier (Plant and Soil, 1999)

Inorganic pollution of the man-made lakes of Wadi El-Raiyan and its impact on aquaculture and wildlife of the surrounding Egyptian desert - Mahmoud Abbas Saleh; Mostafa A. Saleh; Mostafa M. Fouda; Magdy A. Saleh; Mohamed S. Abdel Lattif; Bobby L. Wilson (Archives of Environmental Contamination and Toxicology, 1988)